Stable AIGS film

JP2024516785A5Active Publication Date: 2025-04-07SHOEI CHEM IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023560604
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-03
Filing Date
2022-03-30
Publication Date
2025-04-07
Estimated Expiration
2042-03-30

AI Technical Summary

Technical Problem

Existing green heavy metal-free quantum dot (QD) color conversion films in displays exhibit limited absorption of blue light, leading to poor performance and reduced photon conversion efficiency due to instabilities during processing, necessitating thicker films and inefficient light emission.

Method used

A stable, thin Ag-In-Ga-S (AIGS) nanostructured color conversion film is developed with high photon conversion efficiency (PCE) by using metal alkoxides, metal halides, and ligands, processed in an oxygen-free environment, and encapsulated to withstand yellow light and air exposure, achieving a PCE of over 30% at peak emission wavelengths of 480-545 nm.

Benefits of technology

The AIGS nanostructured film achieves enhanced blue light absorption and emission efficiency, maintaining high PCE even after exposure to yellow light and air, overcoming the limitations of previous QD films by providing a stable and efficient color conversion solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2022212517000001
    Figure 2022212517000001
  • Figure 2022212517000002
    Figure 2022212517000002
Patent Text Reader

Abstract

Disclosed is a stable film comprising Ag, In, Ga, and S (AIGS) nanostructures, one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or combinations thereof, and at least one ligand bound to the nanostructure. In some embodiments, the AIGS nanostructures have a photon conversion efficiency greater than 32% and a peak emission wavelength between 480 and 545 nm. In some embodiments, the nanostructures have an emission spectrum with a FWHM between 24 and 38 nm. In some embodiments, the nanostructures exhibit a photon conversion efficiency (PCE) of at least 30% after 24 hours under yellow light and air storage conditions.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of nanotechnology. More specifically, the present invention provides a thin, heavy metal-free, stable Ag-In-Ga-S color conversion film with a high photon conversion efficiency (PCE) of over 30% at a peak emission wavelength of 480-545 nm when excited using a blue light source having a wavelength of about 450 nm and after exposure to yellow light and air storage conditions. [Background technology]

[0002] Efficient conversion of color is important in lighting and display applications, where blue light sources with a wavelength of about 450 nm are most commonly used as backlights, and many applications require materials that are free of heavy metals such as cadmium and lead.

[0003] The increased efficiency results in less wasted power as well as increased light emission. Color-converting thin films are characterized by their photon conversion efficiency (PCE), defined as the number of emitted photons divided by the number of photons in the light source. Green heavy-metal-free QD color-converting thin films used in displays typically perform poorly due to limited absorption in the blue light they are excited with. Blue absorption is often inherently limited by the material system used, resulting in the need for much thicker films to absorb sufficient 450 nm light.

[0004] The thin films formed by deposition of the QD ink are typically cured by UV irradiation, often followed by a thermal treatment in the presence of air at 180 °C for up to an hour. Instability throughout these processing steps reduces the photon conversion efficiency of these films due to a combination of poor absorption and poor light conversion. Summary of the Invention [Problem to be solved by the invention]

[0005] There remains a need in the art for AIGS nanostructures that have high band edge emission (BE), narrow full width at half maximum (FWHM), high quantum yield (QY), and reduced red shift, and are useful for producing films with high photon conversion efficiency (PCE) (greater than 32% before exposure to yellow light and air storage conditions) at a peak emission wavelength between 480-545 nm using an excitation wavelength of about 450 nm. [Means for solving the problem]

[0006] The present invention provides a thin, heavy metal-free, stable AIGS nanostructured color conversion film with a high photon conversion efficiency (PCE) of greater than 30% at a peak emission wavelength of 480-545 nm when excited using a blue light source having a wavelength of about 450 nm and after intermediate exposure to air under yellow light conditions. This is accomplished by using AIGS nanostructures in an ink formulation containing one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or combinations thereof, and one or more ligands. In some embodiments, all of the ink handling, subsequent film deposition, processing, and measurement are performed in an oxygen-free environment before exposure to blue or ultraviolet light. In some embodiments, the AIGS nanostructures have a FWHM of 28-38 nm. In other embodiments, the AIGS nanostructures have a FWHM of less than 32 nm. In some embodiments, the narrow FWHM is achieved by adding at least one polyamino ligand to the AIGS nanostructures to create the film layer, with all nanostructure ink handling, ink deposition, film processing and measurements being performed in an oxygen-free environment.

[0007] The thin films formed by deposition of the QD ink are typically cured by UV irradiation, often followed by a thermal treatment in the presence of air at 180 °C for up to an hour. Instability throughout these processing steps has been found to reduce the photon conversion efficiency due to a combination of poor absorption and poor light conversion.

[0008] Disclosed herein are films comprising AIGS nanostructures in an ink formulation comprising one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or combinations thereof, and at least one ligand, the films achieving a PCE of greater than (>) 30% after 24 hours of exposure to yellow light and air storage conditions. In some embodiments, films are provided comprising AIGS nanostructures and at least one ligand, and exhibiting a PCE of greater than 32% at a peak emission wavelength of 480-545 nm when excited using a blue light source having a wavelength of about 450 nm. In some embodiments, a film comprising AIGS nanostructures, one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof, and at least one ligand exhibits a PCE of 30-39% after exposure to air, yellow light, and air storage conditions. In some embodiments, a film comprising AIGS nanostructures, one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof, and at least one ligand exhibits a PCE of about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, or about 39% after exposure to yellow light conditions in air.

[0009] In some embodiments, the membrane is a thin (5-15 μm) color converting membrane.

[0010] As prepared, these films have good (>95%) blue absorption but moderate luminescence properties, however, when processed in the absence of oxygen and / or light and / or encapsulated prior to exposure to UV or blue light, the luminescence properties of these films are significantly improved.

[0011] (a) providing an AIGS nanostructure, one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof, and at least one ligand; (b) combining at least one organic resin with the AIGS nanostructure of (a); (c) preparing a first film on the first barrier layer, the first film comprising intermixed AIGS nanostructures, at least one ligand, and at least one organic resin; (d) curing the film by UV irradiation and / or baking; (e) encapsulating the first film between the first barrier layer and the second barrier layer; wherein the encapsulated film exhibits a photon conversion efficiency (PCE) of greater than 30% at a peak emission wavelength of 480-545 nm when excited using a blue light source having a wavelength of about 450 nm and after exposure to yellow light and air storage conditions.

[0012] Also, (f) adding at least one oxygen-reactive material to the mixture of AIGS nanostructures and ligands of (a), adding at least one oxygen-reactive material to the admixture of (b), and / or forming a second film comprising at least one oxygen-reactive material on the first film prepared in (c); and / or (g) Formation of a sacrificial barrier layer on the first film prepared in (c) to temporarily block oxygen and / or water, and measurement of the PCE of the film, followed by removal of the sacrificial barrier layer. A method is provided further comprising:

[0013] Also, (a) encapsulating the membrane prior to heat treatment and / or measurement; (b) the use of oxygen-reactive materials as part of the formulation during heat treatment or light exposure; and / or (c) Temporary blocking of oxygen through the use of a sacrificial barrier layer A method is provided that includes:

[0014] In some embodiments, the nanostructures have an emission spectrum with a FWHM of less than 40 nm. In some embodiments, the nanostructures have an emission spectrum with a FWHM of 24-38 nm. In some embodiments, the nanostructures have an emission spectrum with a FWHM of 27-32 nm. In some embodiments, the nanostructures have an emission spectrum with a FWHM of 29-31 nm.

[0015] In some embodiments, the nanostructures have a QY of 80-99.9%. In some embodiments, the nanostructures have a QY of 85-95%. In some embodiments, the nanostructures have a QY of about 86-94%. In some embodiments, the nanostructures have an OD of 0.8 or greater. 450 / mass(mL·mg -1 ·cm -1 ) where OD is optical density. In some embodiments, the nanostructures have an OD in the inclusive range of 0.8 to 2.5. 450 / mass(mL·mg -1 ·cm -1 In some embodiments, the nanostructures have an OD in the inclusive range of 0.87 to 1.9. 450 / mass(mL·mg -1 ·cm -1 In some embodiments, the nanostructures have an average diameter of less than 10 nm by transmission electron microscopy (TEM). In some embodiments, the average diameter is about 5 nm.

[0016] In some embodiments, at least about 80% of the emission is band-edge emission. In some embodiments, at least about 90% of the emission is band-edge emission. In some embodiments, 92-98% of the emission is band-edge emission. In some embodiments, 93-96% of the emission is band-edge emission.

[0017] In some embodiments, at least one ligand is an amino ligand, a polyamino ligand, a ligand containing a mercapto group, or a ligand containing a silane group. It has been surprisingly found that the use of a polyamino ligand leads to an AIGS-containing film having a FWHM of less than 32 nm.

[0018] In some embodiments, the at least one polyamino ligand is a polyaminoalkane, a polyaminocycloalkane, a polyaminoheterocycle, a polyamino-functionalized silicone, or a polyamino-substituted ethylene glycol. In some embodiments, the polyamino ligand is a C substituted with two or three amino groups. 2~20 Alkane or C 2~20 A polyamino ligand is a cycloalkane, optionally containing one or two amino groups in place of carbon groups. In some embodiments, the polyamino ligand is 1,3-cyclohexanebis(methylamine), 2,2-dimethyl-1,3-propanediamine, or tris(2-aminoethyl)amine.

[0019] In some embodiments, the ligand is a compound of the formula: [ka] During the ceremony, x is 1 to 100; y is 0 to 100, and R 2 is C 1~20 It is an alkyl.

[0020] In some embodiments, x=19, y=3, and R 2 =-CH3.

[0021] In some embodiments, the ligand is a compound of formula II. [ka] In the formula, R 3 and R 4 is independently 3~6 is a secondary or tertiary alkyl group, R 5 is hydrogen or optionally substituted C 1~6 It is an alkyl group.

[0022] In some embodiments, R 3 and R 4 is isopropyl, 2-butyl, 2-pentyl, 3-pentyl, 2-hexyl, 3-hexyl, t-butyl, 2-methyl-2-pentyl, or 3-methyl-3-pentyl.

[0023] In some embodiments, R 5 C 1~6 Optional substituents on the alkyl group include nitro, haloalkoxy, aryloxy, aralkyloxy, alkylthio, sulfonamido, alkylcarbonyl, arylcarbonyl, alkylsulfonyl, arylsulfonyl, ureido, guanidino, carbamate, carboxy, alkoxycarbonyl, carboxyalkyl, or C(═O)R. 7 (In the formula, R 7 is an alkoxy group which may be further substituted by one or more other alkoxy groups.

[0024] In some embodiments, R 7 is expressed by the following formula: CH p (CH2-O-) 4-p (wherein p is 0 to 3).

[0025] In some embodiments, R 7 teeth, [ka] It is.

[0026] In some embodiments, R 7 teeth, [ka] and formula II is [ka] It is.

[0027] In some embodiments, at least one ligand is pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] or 2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diylbis(2-methylpropane-2,1-diyl)bis[3-[3-(tert-butyl)-4-hydroxy-5-methylphenyl]propanoate].

[0028] In some embodiments, the polymer is (3-aminopropyl)trimethoxysilane; (3-mercaptopropyl)triethoxysilane; DL-α-lipoic acid; 3,6-dioxa-1,8-octanedithiol; 6-mercapto-1-hexanol; methoxypolyethyleneglycolamine (mw about 500); poly(ethyleneglycol)methyletherthiol (mw about 800); diethylphenylphosphonite; dibenzyl N,N-diisopropylphosphoramidite; di-tert-butyl N,N-diisopropylphosphoramidite; tris(2-carboxyethyl)phosphine hydrochloride; poly(ethyleneglycol)methyletherthiol (mw about 2000); methoxypolyethyleneglycolamine (mw about 750); acrylamide; or polyethyleneimine. The mw of the polymer is obtained by mass spectrometry.

[0029] In some embodiments, the at least one ligand is a combination of amino polyalkylene oxide (mw about 1000) and methoxypolyethylene glycol amine (mw about 500); amino-polyalkylene oxide (mw about 1000) and 6-mercapto-1-hexanol; amino polyalkylene oxide (mw about 1000) and (3-mercaptopropyl)triethoxysilane; and 6-mercapto-1-hexanol and methoxypolyethylene glycol amine (mw about 500).

[0030] In some embodiments, the one or more metal alkoxides are selected from the group consisting of metal C 1~10 In some embodiments, the metal is titanium, zirconium, hafnium, gallium, or barium.

[0031] In some embodiments, the at least one or more metal alkoxides are selected from the group consisting of zirconium(IV) tetramethoxide, zirconium(IV) tetraethoxide, zirconium(IV) tetra-n-propoxide, zirconium(IV) tetra-isopropoxide, zirconium(IV) tetra-n-butoxide, zirconium(IV) tetra-isobutoxide, zirconium(IV) tetra-n-pentoxide, zirconium(IV) tetra-isopentoxide, zirconium(IV) tetra zirconium(IV) tetra-n-hexoxide, zirconium(IV) tetra-isohexoxide, zirconium(IV) tetra-n-heptoxide, zirconium(IV) tetra-isoheptoxide, zirconium(IV) tetra-n-octoxide, zirconium(IV) tetra-n-isooctoxide, zirconium(IV) tetra-n-nonoxide, zirconium(IV) tetra-n-isononoxide, zirconium(IV) tetra-n-decyloxide, or zirconium(IV) tetra-n-isodecyloxide.

[0032] In some embodiments, the at least one or more metal alkoxides is zirconium(IV) tetra-n-propoxide.

[0033] In some embodiments, the one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof is zirconium(IV) tetra n-propoxide, and the membrane further comprises pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] or 2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diylbis(2-methylpropane-2,1-diyl)bis[3-[3-(tert-butyl)-4-hydroxy-5-methylphenyl]propanoate].

[0034] Also, (a) AIGS nanostructures exhibiting a PCE higher than 30% after exposure to yellow light and air storage conditions; (b) at least one organic resin; Also provided is a nanostructure composition comprising:

[0035] In some embodiments, the at least one organic resin is cured.

[0036] Also, (a) providing an AIGS nanostructure, one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof, and at least one ligand; (b) combining at least one organic resin with the nanostructures of (a); (c) preparing a first film on the first barrier layer, the first film comprising intermixed AIGS nanostructures, at least one ligand, and at least one organic resin; (d) curing the film by UV irradiation and / or baking; and (e) encapsulating the first film between the first barrier layer and the second barrier layer; Provided is a method of preparing the nanostructure composition described herein, comprising:

[0037] In some embodiments, the method is performed before exposing the encapsulated film to the emission spectrum of the AIGS nanostructures in air, hi some embodiments, the method is performed under an inert atmosphere.

[0038] In some embodiments, the method comprises: (f) the addition of at least one oxygen-reactive material in the mixture of the AIGS nanostructures of (a), one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof, and ligand; (g) the addition of at least one oxygen-reactive material in the admixture of (b); and / or (h) forming a second film comprising at least one oxygen-reactive material on the first film prepared in (c); and / or (i) Formation of a sacrificial barrier layer on the first film prepared in (c) to temporarily block oxygen and / or water, and measurement of the PCE of the film, followed by removal of the sacrificial barrier layer. Further includes:

[0039] In some embodiments, the two barrier layers exclude oxygen and / or water.

[0040] In some embodiments, 92-98% of the emission is band-edge emission, hi some embodiments, 93-96% of the emission is band-edge emission.

[0041] Also, (a) providing a solvent comprising an AIGS nanostructure, one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof, and at least one ligand; (b) combining the composition obtained in (a) with at least one second ligand; Also provided is a method for preparing the composition, comprising:

[0042] In some embodiments, the (a) solvent comprises an organic resin, hi some embodiments, the method comprises inkjet printing the composition.

[0043] In some embodiments, the method further comprises preparing a film comprising the composition obtained in (b). In some embodiments, the method further comprises curing the film. In some embodiments, the film is cured by heating. In some embodiments, the film is cured by exposure to electromagnetic radiation.

[0044] Also provided is a device comprising the membrane described above.

[0045] Also, (a) a first conductive layer; (b) a second conductive layer; and (c) a film including an AIGS nanostructured layer between a first conductive layer and a second conductive layer; Also provided is a nanostructured molded article comprising:

[0046] Also A backplane; a display panel disposed on the backplane; a film comprising an AIGS nanostructure having a PCE of greater than 30% after exposure to yellow light and air storage conditions, the film comprising an AIGS nanostructure layer disposed on a display panel; A color converter is also provided, including

[0047] In some embodiments, the nanostructured layer comprises a patterned nanostructured layer, hi some embodiments, the backplane comprises an LED, an LCD, an OLED, or a micro LED.

[0048] Further features and advantages of the present invention, as well as the structure and operation of various embodiments of the present invention, are described in detail below with reference to the accompanying drawings. It should be noted that the present invention is not limited to the specific embodiments described herein. Such embodiments are presented herein for illustrative purposes only. Based on the teachings contained herein, additional embodiments will be apparent to those skilled in the relevant art.

[0049] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate the present embodiments and, together with the description, serve to explain the principles of the present embodiments and to assist those skilled in the relevant art in making and using the embodiments. [Brief description of the drawings]

[0050] [Figure 1] Photographs (from left to right) of the first and third films, which did not contain polyamino ligands and showed elongation wrinkles. The second and fourth films, which contained polyamino ligands, did not show wrinkles. [Diagram 2] 2A and 2B are TEM images showing the AIGS nanostructure before ion-exchange treatment (FIG. 2A), after one ion-exchange treatment (FIG. 2B), and after two ion-exchange treatments (FIG. 2C). [Diagram 3]Schematic diagram of unencapsulated (FIG. 3A) and encapsulated (FIG. 3B) membranes. [Figure 4] 1 is a scatter graph showing the QY% exhibited by various mixtures of ligands. [Diagram 5] 1 is a scatter graph showing ligand combinations that provide improved QY% (good combinations) and combinations that provide reduced QY% (bad combinations). [Figure 6] 1 is a graph showing the QY% of various ligand combinations before ligand exchange (NG), after ligand exchange (LE), and after a 30 minute heat test. [Figure 7] 1 is a graph showing the QY% of various ligand combinations at various ligand ratios. [Figure 8] 1 is two scatter graphs showing the PCE of an AIGS film after normal PCE measurements and after encapsulation. [Figure 9] 1 is two scatter graphs showing the PCE of AIGS films fired at 180° C. without (left graph) and with (right graph) encapsulation prior to PCE measurement. [Figure 10] 1 is a line graph showing EQE % versus blue light absorbance of thin films of AIGS ink formulations after ancillary ligand exchange. [Figure 11] 1 is a line graph showing EQE % over time for thin films of AIGS ink formulations containing various ancillary ligands when kept in the dark. [Figure 12] 1 is a line graph showing EQE % over time for thin films of AIGS ink formulations containing various ancillary ligands when exposed to yellow light conditions. [Figure 13] 1 is a line graph showing EQE% over time for thin films of AIGS ink formulations containing various ancillary ligands and additives when exposed to yellow light conditions. [Figure 14] FIG. 1 is a line graph showing EQE % versus blue light absorbance of thin films of AIGS ink formulations containing ancillary ligand-1; ancillary ligand-1 and zirconium propoxide (S2); ancillary ligand-1, S2 and GaCl3 (S3); and S2 and S3. [Figure 15]1 is a bar graph showing the EQE of AIGS films containing subligand-1; subligand-1 and S2; subligand-1, S2 and S3; and S2 and S3 after baking under nitrogen. [Figure 16] 1 is a line graph showing EQE % over time for cured AIGS films containing ancillary ligand-1; ancillary ligand-1 and S2; ancillary ligand-1, S2 and S3; and S2 and S3 when exposed to yellow light conditions. [Figure 17] 1 is a line graph showing EQE% versus blue light absorbance for AIGS films containing 1% S3, 3% S3, and 6% S3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0051] The features and advantages of the present invention will become more apparent from the detailed description set forth below when considered in conjunction with the drawings, in which like reference characters identify corresponding elements throughout. In the drawings, like reference numbers generally indicate identical, functionally similar, and / or structurally similar elements. The drawing in which an element first appears is indicated by the leftmost digit(s) of the corresponding reference number. Unless otherwise indicated, the drawings provided throughout this disclosure should not be construed as drawings to scale.

[0052] definition Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by ordinary skilled artisans to which the present invention pertains. The following definitions supplement the definitions in the art and relate to this application, and are not attributable to any related or unrelated cases, such as any commonly owned patents or applications. Although any methods and materials similar or equivalent to those described herein can be used to carry out the testing of the present invention, the preferred materials and methods are described herein. Therefore, the terms used herein are for the purpose of describing specific embodiments only, and are not intended to be limiting.

[0053] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Thus, for example, reference to "a nanostructure" includes a plurality of such nanostructures, and the like.

[0054] As used herein, the term "about" indicates that a given quantity value varies by ±10% of that value. For example, "about 100 nm" encompasses the size range from 90 nm to 110 nm.

[0055] A "nanostructure" is a structure having at least one region or characteristic dimension having a dimension less than about 500 nm. In some embodiments, a nanostructure has a dimension less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm. Typically, the region or characteristic dimension is along the smallest axis of the structure. Examples of such structures include nanowires, nanorods, nanotubes, branched nanostructures, nanotetrapods, tripods, bipods, nanocrystals, nanodots, quantum dots, nanoparticles, and the like. Nanostructures can be, for example, substantially crystalline, substantially monocrystalline, polycrystalline, amorphous, or combinations thereof. In some embodiments, each of the three dimensions of a nanostructure has a dimension less than about 500 nm, less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm.

[0056] The term "heterostructure" when used with respect to nanostructures means a nanostructure characterized by at least two different and / or distinguishable material types. Typically, one region of the nanostructure comprises a first material type and a second region of the nanostructure comprises a second material type. In certain embodiments, the nanostructure comprises a core of a first material and at least one shell of a second (or third, etc.) material, where the different material types are distributed radially, for example, relative to the long axis of a nanowire, the long axis of an arm of a branched nanowire, or the center of a nanocrystal. A shell can, but need not, completely cover an adjacent material to be considered a shell, or in terms of a nanostructure, a heterostructure. For example, a nanocrystal characterized by a core of one material covered by small islands of a second material is a heterostructure. In other embodiments, the different material types are distributed at different locations within the nanostructure, for example, along the major (long) axis of a nanowire or along the long axis of an arm of a branched nanowire. Different regions within a heterostructure can comprise entirely different materials, or the different regions can comprise a base material (eg, silicon) with different dopants or different concentrations of the same dopant.

[0057] As used herein, the "diameter" of a nanostructure refers to the diameter of a cross section perpendicular to a first axis of the nanostructure, where the first axis has the greatest length difference with respect to the second and third axes (the second and third axes being the two axes whose lengths are most nearly equal to each other). The first axis is not necessarily the longest axis of the nanostructure, for example, in a disk-shaped nanostructure, the cross section is a substantially circular cross section perpendicular to the short longitudinal axis of the disk. If the cross section is not circular, the diameter is the average of the long and short axes of the cross section. For elongated nanostructures such as nanowires or nanostructures with high aspect ratios, the diameter is measured across a cross section perpendicular to the longest axis of the nanowire. For spherical nanostructures, the diameter is measured from one side through the center of the sphere to the other side.

[0058] The term "crystalline" or "substantially crystalline" when used in reference to a nanostructure refers to the fact that the nanostructure typically exhibits long-range order across one or more dimensions of the structure. One skilled in the art will appreciate that the term "long-range order" depends on the absolute size of a particular nanostructure, since single-crystal order cannot exceed the boundaries of the crystal. In this case, "long-range ordering" refers to substantial ordering across at least the majority of the dimensions of the nanostructure. In some cases, the nanostructure may have an oxide or other coating, or may be composed of a core and at least one shell. In such cases, it will be understood that the oxide, shell, or other coating may, but need not, exhibit such order (e.g., may be amorphous, polycrystalline, or otherwise). In such cases, the phrases "crystalline," "substantially crystalline," "substantially monocrystalline," or "monocrystalline" refer to the central core of the nanostructure (excluding any coating layers or shells). As used herein, the terms "crystalline" or "substantially crystalline" are intended to encompass structures that contain various defects, stacking faults, atomic substitutions, and the like, so long as the structure exhibits substantial long-range order (e.g., order over at least about 80% of the length of at least one axis of the nanostructure or its core). In addition, it will be understood that the interface between the core and the exterior of the nanostructure, the interface between the core and an adjacent shell, or the interface between a shell and a second adjacent shell may include non-crystalline regions and may be amorphous. This does not prevent a nanostructure from being crystalline or substantially crystalline as defined herein.

[0059] When used in reference to a nanostructure, the term "monocrystalline" indicates that the nanostructure is substantially crystalline and comprises substantially a single crystal. When used in reference to a nanostructure heterostructure comprising a core and one or more shells, "monocrystalline" indicates that the core is substantially crystalline and comprises substantially a single crystal.

[0060] A "nanocrystal" is a nanostructure that is substantially monocrystalline. Thus, a nanocrystal is a structure having at least one region or characteristic dimension with a dimension of less than about 500 nm. In some embodiments, a nanocrystal has a dimension of less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm. The term "nanocrystal" is intended to encompass substantially monocrystalline nanostructures that contain various defects, stacking faults, atomic substitutions, and the like, as well as substantially monocrystalline nanostructures that are free of such defects, imperfections, or substitutions. In the case of nanocrystal heterostructures that include a core and one or more shells, the core of the nanocrystal is typically substantially monocrystalline, but the shells need not be. In some embodiments, each of the three dimensions of the nanocrystal has a dimension of less than about 500 nm, less than about 200 nm, less than about 100 nm, less than about 50 nm, less than about 20 nm, or less than about 10 nm.

[0061] The term "quantum dot" (or "dot") refers to nanocrystals that exhibit quantum or exciton confinement. Quantum dots can be substantially homogeneous in material properties or in certain embodiments can be heterogeneous, e.g., comprising a core and at least one shell. The optical properties of quantum dots can be affected by their particle size, chemical composition, and / or surface composition, and can be measured by suitable optical tests available in the art. The ability to tune nanocrystal size, e.g., from about 1 nm to about 15 nm, allows light emission in the entire optical spectral range, providing a large variety of color rendering properties.

[0062] The term "oxygen-free ligand" as used herein means a coordinating molecule that does not contain an oxygen atom capable of coordinating to or reacting with a metal ion.

[0063] A "ligand" is a molecule that can interact (either weakly or strongly) with one or more faces of a nanostructure, for example, through covalent bonds, ionic bonds, van der Waals bonds, or other molecular interactions with the surface of the nanostructure.

[0064] "Photoluminescence quantum yield" (QY), for example, is the ratio of photons emitted to photons absorbed by a nanostructure or ensemble of nanostructures. As known in the art, quantum yield is usually determined by the absolute change in photon count upon illumination of a sample in an integrating sphere, or by comparative methods using well-characterized standards with known quantum yield values.

[0065] "Peak emission wavelength" (PWL) is the wavelength at which the radiative emission spectrum of a light source reaches a maximum.

[0066] As used herein, the term "full width at half-maximum" (FWHM) is a measure of the size distribution of nanostructures. The emission spectrum of a nanostructure generally has the shape of a Gaussian curve. The width of the Gaussian curve is defined as the FWHM and is a measure of the size distribution of the particles. A smaller FWHM corresponds to a narrower nanocrystal size distribution of the nanostructure. The FWHM also depends on the maximum emission wavelength.

[0067] The band-edge emission has a smaller offset from the absorption onset energy and is centered at higher energy (lower wavelength) compared to the defect emission. Furthermore, the band-edge emission has a narrower wavelength distribution compared to the defect emission. Both the band-edge and defect emissions follow normal (approximately Gaussian) wavelength distributions.

[0068] Optical density (OD) is a commonly used method to quantify the concentration of solutes or nanoparticles. According to the Beer-Lambert law, the absorbance (also called "extinction") of a particular sample is proportional to the concentration of the solute that absorbs light of a particular wavelength.

[0069] Optical density is the light attenuation per centimeter of a material measured using a standard spectrometer and is usually specified in terms of centimeters of optical path length. Nanostructure solutions are often measured by optical density instead of mass or molar concentration because it is directly proportional to concentration and is a more convenient way to express the amount of light absorption occurring in the nanostructure solution at the wavelength of interest. A nanostructure solution with an OD of 100 is 100 times more concentrated (has 100 times more particles per mL) than a product with an OD of 1.

[0070] Optical density can be measured at any wavelength of interest, such as the wavelength selected to excite fluorescent nanostructures. Optical density is a measure of the intensity lost when light at a particular wavelength passes through a solution of nanostructures, and is given by the following formula: OD=log 10 * (I OUT / I IN ) It is calculated using I OUT = the intensity of radiation incident on the cell, and I IN = the intensity of radiation transmitted through the cell.

[0071] The optical density of the nanostructure solution can be measured using a UV-VIS spectrometer. Thus, by using a UV-VIS spectrometer, it is possible to calculate the optical density to determine the amount of nanostructures present in a sample.

[0072] "Yellow light and air storage condition" is intended to mean a film illuminated in air using a white LED light coated with a blue blocking filter, the illuminance and color coordinates of the yellow storage condition are measured by a Konica-Minolta CL-200A chromameter as 140 lux, CIEx=0.52, CIEy=0.45.

[0073] Unless expressly indicated otherwise, the ranges set forth herein are inclusive.

[0074] Various additional terms are defined or otherwise characterized herein.

[0075] AIGS Nanostructure Nanostructures comprising Ag, In, Ga, and S (AIGS) are provided, the nanostructures having a peak emission wavelength (PWL) between 480-545 nm. In some embodiments, at least about 80% of the emission is band-edge emission. The percentage of band-edge emission is calculated by fitting a Gaussian peak (typically two or more) of the nanostructure emission spectrum and comparing the area of ​​the peak close in energy to the nanostructure band gap (which represents the band-edge emission) to the sum of all peak areas (band-edge + defect emission).

[0076] In one embodiment, the nanostructures have an emission spectrum with a FWHM of less than 40 nm. In another embodiment, the nanostructures have an FWHM of 36-38 nm. In some embodiments, the nanostructures have an emission spectrum with a FWHM of 27-32 nm. In some embodiments, the nanostructures have an emission spectrum with a FWHM of 29-31 nm.

[0077] In another embodiment, the nanostructures have a QY of about 80%-99.9%. In another embodiment, the nanostructures have a QY of 85-95%. In another embodiment, the nanostructures have a QY of about 86%-about 94%. In some embodiments, at least 80% of the emission is band-edge emission. In other embodiments, at least 90% of the emission is band-edge emission. In other embodiments, at least 95% of the emission is band-edge emission. In some embodiments, 92-98% of the emission is band-edge emission. In some embodiments, 93-96% of the emission is band-edge emission.

[0078] AIGS nanostructures provide high blue light absorption. The optical density at 450 nm (OD ) per mass is used as a predictor of blue light absorption efficiency. 450The optical density (mg / mass) is calculated by measuring the optical density of the nanostructure solution in a 1 cm path length cuvette and dividing by the dry mass (mg / mL) per mL of the same solution after removing all volatiles under vacuum (<200 mTorr). In one embodiment, the nanostructures provided herein have an OD of at least 0.8. 450 / mass(mL·mg -1 ·cm -1 In another embodiment, the nanostructures have an OD of 0.8 to 2.5. 450 / mass(mL·mg -1 ·cm -1 In another embodiment, the nanostructures have an OD of 0.87 to 1.9. 450 / mass(mL·mg -1 ·cm -1 ).

[0079] In one embodiment, the nanostructures are treated with gallium ions such that ion exchange of gallium for indium occurs throughout the AIGS nanostructure. In another embodiment, the nanostructures have Ag, In, Ga, and S in the core and are treated by ion exchange with gallium ions and S. In another embodiment, the nanostructures have Ag, In, Ga, and S in the core and are treated by ion exchange with silver ions, gallium ions, and S. In some embodiments, the ion exchange process leads to gradients of gallium, silver, and / or sulfur throughout the nanostructure.

[0080] In one embodiment, the nanostructures have an average diameter of less than 10 nm as measured by TEM, hi another embodiment, the average diameter is about 5 nm.

[0081] AIGS nanostructures prepared using GaX3 (X=F, Cl, or Br) precursors and oxygen-free ligands No attempt has been made in the literature to exclude oxygen-containing ligands. In the coating of AIGS with gallium, oxygen-containing ligands are often used to stabilize the Ga precursor. Generally, gallium(III) acetylacetate is used as a precursor that can be easily handled in air, while Ga(III) chloride is sensitive to moisture and must be handled with care. For example, in Kameyama et al., ACS Appl. Matera. Interfaces 10:42844-42855 (2018), gallium(III) acetylacetate was used as a precursor for core and core / shell structures. Since gallium has a high affinity for oxygen and oxygen-containing ligands, undesirable side reactions, such as gallium oxide, can occur when using gallium precursors that are not prepared under oxygen-free conditions to produce nanostructures with significant gallium content using Ga and S precursors. These side reactions can lead to defects in the nanostructures and result in low quantum yields.

[0082] In some embodiments, AIGS nanostructures are prepared using oxygen-free GaX3 (X=F, Cl, or Br) as precursors in the preparation of the AIGS core. In some embodiments, AIGS nanostructures are prepared using GaX3 (X=F, Cl, or Br) and oxygen-free ligands as precursors in the preparation of Ga-rich AIGS nanostructures. In some embodiments, AIGS nanostructures are prepared using GaX3 (X=F, Cl, or Br) and oxygen-free ligands as precursors in the preparation of the AIGS core. In some embodiments, AIGS nanostructures are prepared using GaX3 (X=F, Cl, or Br) and oxygen-free ligands as precursors in the preparation of the AIGS core and ion exchange treatment of the AIGS core.

[0083] Nanostructures comprising Ag, In, Ga, and S are provided, having a peak emission wavelength (PWL) between 480-545 nm, prepared using GaX3 (X=F, Cl, or Br) precursors and oxygen-free ligands.

[0084] In some embodiments, nanostructures prepared using GaX3 (X=F, Cl, or Br) precursors and oxygen-free ligands exhibit a FWHM emission spectrum of 35 nm or less. In some embodiments, nanostructures prepared using GaX3 (X=F, Cl, or Br) precursors and oxygen-free ligands exhibit a FWHM of 30-38 nm. In some embodiments, nanostructures prepared using GaX3 (X=F, Cl, or Br) precursors and oxygen-free ligands have a QY of at least 75%. In some embodiments, nanostructures prepared using GaX3 (X=F, Cl, or Br) precursors and oxygen-free ligands have a QY of 75-90%. In some embodiments, nanostructures prepared using GaX3 (X=F, Cl, or Br) precursors and oxygen-free ligands have a QY of about 80%.

[0085] The AIGS nanostructures prepared herein provide high blue light absorption. In some embodiments, the nanostructures have an OD of at least 0.8. 450 / mass(mL·mg -1 ·cm -1 In some embodiments, the nanostructures have an OD of 0.8 to 2.5. 450 / mass(mL·mg -1 ·cm -1 In another embodiment, the nanostructures have an OD of 0.87 to 1.9. 450 / mass(mL·mg -1 ·cm -1 ).

[0086] In some embodiments, the nanostructures are treated with gallium ions such that ion exchange of gallium for indium occurs throughout the AIGS nanostructure. In some embodiments, the nanostructures include Ag, In, Ga, and S in the core with a gallium gradient between the surface and center of the nanostructure. In some embodiments, the nanostructures are AIGS cores treated with AIGS and prepared using GaX3 (X=F, Cl, or Br) precursors and oxygen-free ligands in the core. In some embodiments, the nanostructures are AIGS nanostructures prepared using GaX3 (X=F, Cl, or Br) precursors and oxygen-free ligands. In some embodiments, the AIGS nanostructures are prepared by reacting a preformed In-Ga reagent with Ag2S nanostructures to obtain AIGS nanostructures, which are then reacted with an oxygen-free Ga salt to ion exchange with gallium to form the AIGS nanostructures.

[0087] Fabrication of AIGS nanostructures A method for producing an AIGS nanostructure, comprising the steps of: (a) preparing a mixture comprising an AIGS core, a sulfur source, and a ligand; (b) adding the mixture obtained in (a) to a mixture of gallium carboxylate and ligand at a temperature of 180-300° C. to obtain an ion-exchanged nanostructure having a gradient of gallium from the surface to the center of the nanostructure; (c) isolating the nanostructures; A method is provided that includes:

[0088] In some embodiments, the nanostructures have a PWL between 480 and 545 nm, with at least about 60% of the emission being band edge emission.

[0089] There is also provided a method for producing an AIGS nanostructure, comprising the steps of: (a) reacting Ga(acetylacetonate), InCl, and a ligand, optionally in a solvent, at a temperature sufficient to obtain an In-Ga reagent; (b) reacting an In-Ga reagent with the Ag2S nanostructure at a temperature sufficient to produce an AIGS nanostructure; (c) reacting the AIGS nanostructure with an oxygen-free Ga salt in a solvent containing the ligand at a temperature sufficient to obtain an ion-exchanged nanostructure having a gallium gradient from the surface to the center of the nanostructure; Also provided is a method comprising:

[0090] In some embodiments, the nanostructures have a PWL between 480 and 545 nm, with at least about 60% of the emission being band edge emission.

[0091] In some embodiments, the ligand is an alkylamine. In some embodiments, the alkylamine ligand is oleylamine. In some embodiments, the ligand is used in excess and acts as a solvent, and the cited solvent is not present in the reaction. In some embodiments, a solvent is present in the reaction. In some embodiments, the solvent is a high boiling solvent. In some embodiments, the solvent is octadecene, squalane, dibenzyl ether, or xylene. In some embodiments, the sufficient temperature in (a) is 100-280°C, the sufficient temperature in (b) is 150-260°C, and the sufficient temperature in (c) is 170-280°C. In some embodiments, the sufficient temperature in (a) is about 210°C, the sufficient temperature in (b) is about 210°C, and the sufficient temperature in (c) is about 240°C.

[0092] In some embodiments, at least 80% of the emission is band-edge emission. In other embodiments, at least 90% of the emission is band-edge emission. In other embodiments, at least 95% of the emission is band-edge emission. In some embodiments, 92-98% of the emission is band-edge emission. In some embodiments, 93-96% of the emission is band-edge emission.

[0093] Examples of ligands are disclosed in U.S. Patent Nos. 7,572,395, 8,143,703, 8,425,803, 8,563,133, 8,916,064, 9,005,480, 9,139,770, and 9,169,435, and U.S. Patent Publication No. 2008 / 0118755. In one embodiment, the ligand is an alkylamine. In some embodiments, the ligand is an alkylamine selected from the group consisting of dodecylamine, oleylamine, hexadecylamine, dioctylamine, and octadecylamine.

[0094] In some embodiments, the sulfur source of (a) comprises trioctylphosphine sulfide, elemental sulfur, octanethiol, dodecanethiol, octadecanethiol, tributylphosphine sulfide, cyclohexyl isothiocyanate, α-toluenethiol, ethylene trithiocarbonate, allyl mercaptan, bis(trimethylsilyl) sulfide, trioctylphosphine sulfide, or a combination thereof. In some embodiments, the sulfur source of (a) is derived from S8.

[0095] In one embodiment, the sulfur source is derived from S8.

[0096] In one embodiment, the temperature in (a) and (b) is about 270°C.

[0097] In one embodiment, the mixture of (b) further comprises a solvent, hi some embodiments, the solvent is trioctylphosphine, dibenzyl ether, or squalane.

[0098] In some embodiments, the gallium carboxylate is 2~24 Gallium carboxylate. C 2~24Examples of carboxylates include acetate, propionate, butanoate, pentanoate, hexanoate, heptanoate, octanoate, nonanoate, decanoate, undecanoate, tridecanoate, tetradecanoate, pentadecanoate, hexadecanoate, octadecanoate (oleate), nonadecanoate, and icosanoate. In one embodiment, the gallium carboxylate is gallium oleate.

[0099] In some embodiments, the ratio of gallium carboxylate to AIGS core is 0.008-0.2 mmol of gallium carboxylate per mg of AIGS, hi one embodiment, the ratio of gallium carboxylate to AIGS core is about 0.04 mmol of gallium carboxylate per mg of AIGS.

[0100] In further embodiments, the AIGS nanostructures are isolated, for example, by precipitation. In some embodiments, the AIGS nanostructures are precipitated by the addition of a non-solvent for the AIGS nanostructures. In some embodiments, the non-solvent is a toluene / ethanol mixture. The precipitated nanostructures can be further isolated by centrifugation and washing with a non-solvent for the nanostructures.

[0101] There is also provided a method for producing a nanostructure, comprising the steps of: (a) preparing a mixture comprising an AIGS core and a gallium halide in a solvent and holding the mixture for a time sufficient to obtain an ion-exchanged nanostructure having a gradient of gallium from the surface to the center of the nanostructure; (b) Isolating the nanostructures and A method is provided that includes:

[0102] In some embodiments, the nanostructures have a PWL between 480 and 545 nm, with at least about 60% of the emission being band edge emission.

[0103] In some embodiments, at least 80% of the emission is band-edge emission. In other embodiments, at least 90% of the emission is band-edge emission. In other embodiments, at least 95% of the emission is band-edge emission.

[0104] In some embodiments, the gallium halide is gallium chloride, gallium bromide, or gallium iodide. In one embodiment, the gallium halide is gallium iodide.

[0105] In some embodiments, the solvent comprises trioctylphosphine, hi some embodiments, the solvent comprises toluene.

[0106] In some embodiments, the sufficient time in (a) is 0.1 to 200 hours. In some embodiments, the sufficient time in (a) is about 20 hours.

[0107] In some embodiments, the mixture is kept at 20-100° C. In one embodiment, the mixture is kept at about room temperature (20° C.-25° C.).

[0108] In some embodiments, the molar ratio of gallium halide to the AIGS core is from about 0.1 to about 30.

[0109] In further embodiments, the AIGS nanostructures are isolated, for example, by precipitation. In some embodiments, the AIGS nanostructures are precipitated by the addition of a non-solvent for the AIGS nanostructures. In some embodiments, the non-solvent is a toluene / ethanol mixture. The precipitated nanostructures can be further isolated by centrifugation and / or washing with a non-solvent for the nanostructures.

[0110] There is also provided a method for producing a nanostructure, comprising the steps of: (a) preparing a mixture comprising an AIGS nanostructure, a sulfur source, and a ligand; (b) adding the mixture obtained in (a) to a mixture of GaX3 (X=F, Cl, or Br) and oxygen-free ligands at a temperature of 180-300° C. to obtain an ion-exchanged nanostructure having a gallium gradient from the surface to the center of the nanostructure; (c) isolating the nanostructures; A method is also provided that includes:

[0111] In some embodiments, the nanostructures have a PWL of 480-545 nm.

[0112] In some embodiments, the preparation of (a) is carried out under oxygen-free conditions. In some embodiments, the preparation of (a) is carried out in a glove box.

[0113] In some embodiments, the addition of (b) is under oxygen-free conditions. In some embodiments, the addition of (b) is performed in a glove box.

[0114] In some embodiments, at least 80% of the emission is band-edge emission. In other embodiments, at least 90% of the emission is band-edge emission. In other embodiments, at least 95% of the emission is band-edge emission.

[0115] Examples of ligands are disclosed in U.S. Patent Nos. 7,572,395, 8,143,703, 8,425,803, 8,563,133, 8,916,064, 9,005,480, 9,139,770, and 9,169,435, and U.S. Patent Publication No. 2008 / 0118755. In some embodiments, the ligand of (a) is an oxygen-free ligand. In some embodiments, the ligand of (b) is an oxygen-free ligand. In some embodiments, the ligands of (a) and (b) are alkylamines. In some embodiments, the ligand is an alkylamine selected from the group consisting of dodecylamine, oleylamine, hexadecylamine, dioctylamine, and octadecylamine. In some embodiments, the ligand in (a) is oleylamine. In some embodiments, the ligand in (b) is oleylamine. In some embodiments, the ligand in (a) and (b) is oleylamine.

[0116] In one embodiment, the sulfur source is derived from S8.

[0117] In one embodiment, the temperature in (a) and (b) is about 270°C.

[0118] In one embodiment, the mixture of (b) further comprises a solvent, hi some embodiments, the solvent is trioctylphosphine, dibenzyl ether, or squalane.

[0119] In some embodiments, GaX3 is gallium chloride, gallium fluoride, or gallium iodide. In some embodiments, GaX3 is gallium chloride. In some embodiments, GaX3 is Ga(III) chloride.

[0120] In some embodiments, the molar ratio of GaX3 to the AIGS core is 0.008 to 0.2 mmol of GaX3 per mg of AIGS. In some embodiments, the molar ratio of GaX3 to the AIGS core is about 0.1 to about 30. In some embodiments, the ratio of GaX3 to the AIGS core is about 0.04 mmol of GaX3 per mg of AIGS.

[0121] In some embodiments, the AIGS nanostructures are isolated, for example, by precipitation. In some embodiments, the AIGS nanostructures are precipitated by the addition of a non-solvent for the AIGS nanostructures. In some embodiments, the non-solvent is a toluene / ethanol mixture. The precipitated nanostructures can be further isolated by centrifugation and / or washing with a non-solvent for the nanostructures.

[0122] In some embodiments, the mixture (a) is maintained at 20° C. to 100° C. In some embodiments, the mixture (a) is maintained at about room temperature (20° C. to 25° C.).

[0123] In some embodiments, the mixture (b) is held at 200° C. to 300° C. for 0.1 hours to 200 hours. In some embodiments, the mixture (b) is held at 200° C. to 300° C. for about 20 hours.

[0124] Doped AIGS nanostructures In some embodiments, the AIGS nanostructure is doped. In some embodiments, the dopant of the nanocrystalline core is composed of a metal, including one or more transition metals. In some embodiments, the dopant is a transition metal selected from the group consisting of Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Mn, Tc, Re, Fe, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, and combinations thereof. In some embodiments, the dopant comprises a non-metal. In some embodiments, the dopant is ZnS, ZnSe, ZnTe, CdSe, CdS, CdTe, HgS, HgSe, HgTe, CuInS2, CuInSe2, AlN, AlP, AlAs, GaN, GaP, or GaAs.

[0125] In some embodiments, the cores are purified by precipitation from a non-solvent, hi some embodiments, the AIGS nanostructures are filtered to remove precipitates from the core solution.

[0126] Nanostructured Compositions In some embodiments, the present disclosure provides: (a) at least one AIGS nanostructure; (b) at least one organic resin; A nanostructure composition is provided comprising:

[0127] In some embodiments, the nanostructures have a PWL of 480-545 nm.

[0128] In some embodiments, at least 80% of the nanostructure emission is band-edge emission. In other embodiments, at least 90% of the emission is band-edge emission. In other embodiments, at least 95% of the emission is band-edge emission. In some embodiments, 92-98% of the emission is band-edge emission. In some embodiments, 93-96% of the emission is band-edge emission.

[0129] In some embodiments, the nanostructure composition further comprises at least one second population of nanostructures. The nanostructures having a PWL between 480 and 545 nm emit green light. Additional populations of nanostructures may be added that emit in the green, yellow, orange, and / or red regions of the spectrum. These nanostructures have a PWL greater than 545 nm. In some embodiments, the nanostructures have a PWL between 550 and 750 nm. The size of the nanostructures determines the emission wavelength. The at least one second population of nanostructures may comprise III-V nanocrystals selected from the group consisting of BN, BP, BAs, BSb, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, and InSb. In some embodiments, the cores of the second population of nanostructures are InP nanocrystals.

[0130] Organic Resin In some embodiments, the organic resin is a thermoset resin or an ultraviolet (UV) curable resin. In some embodiments, the organic resin is cured by a method that facilitates roll-to-roll processing.

[0131] Thermosetting resins require curing through an irreversible molecular crosslinking process that makes the resin injectable. In some embodiments, the thermosetting resin is an epoxy resin, a phenolic resin, a vinyl resin, a melamine resin, a urea resin, an unsaturated polyester resin, a polyurethane resin, an aryl resin, an acrylic resin, a polyamide resin, a polyamide-imide resin, a phenolamine condensation polymerization resin, a urea-melamine condensation polymerization resin, or a combination thereof.

[0132] In some embodiments, the thermosetting resin is an epoxy resin. Epoxy resins cure easily with a wide range of chemicals without generating volatiles or by-products. Epoxy resins are also compatible with most substrates and tend to wet surfaces easily. See Boyle, MA et al, "Epoxy Resins", Composites, Vol. 21, ASM Handbook, pages 78-89 (2001).

[0133] In some embodiments, the organic resin is a silicone thermoset. In some embodiments, the silicone thermoset is OE6630A or OE6630B (Dow Corning Corporation, Auburn, Mich.).

[0134] In some embodiments, a thermal initiator is used, hi some embodiments, the thermal initiator is AIBN [2,2'-azobis(2-methylpropionitrile)] or benzoyl peroxide.

[0135] A UV-curable resin is a polymer that cures and hardens quickly when exposed to light of a specific wavelength. In some embodiments, the UV-curable resin is a resin having a radical polymerizable group such as a (meth)acryloyloxy group, a vinyloxy group, a styryl group, or a vinyl group; or a cationic polymerizable group such as an epoxy group, a thioepoxy group, a vinyloxy group, or an oxetanyl group as a functional group. In some embodiments, the UV-curable resin is a polyester resin, a polyether resin, a (meth)acrylic resin, an epoxy resin, a urethane resin, an alkyd resin, a spiroacetal resin, a polybutadiene resin, or a polythiolpolyene resin.

[0136] In some embodiments, the UV curable resin is selected from the group consisting of isobornyl acrylate, isobornyl methacrylate, phenoxyethyl acrylate, phenoxyethyl methacrylate, urethane acrylate, allyloxylated cyclohexyl diacrylate, bis(acryloyloxyethyl)hydroxyl isocyanurate, bis(acryloyloxyneopentyl glycol) adipate, bisphenol A diacrylate, bisphenol A dimethacrylate, 1,4-butanediol diacrylate, 1,4-butanediol dimethacrylate, 1,3-butylene glycol diacrylate, 1,3-butylene glycol dimethacrylate, dicyclopentanyl diacrylate, diethylene glycol diacrylate, diethylene glycol dimethacrylate, dipentaerythritol hexaacrylate, dipentaerythritol monohydroxypentaacrylate, di(trimethylolpropane)tetraacrylate, ethylene glycol dimethacrylate, glycerol methacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol diacrylate, 1,7-hexanediol dimethacrylate, 1,8-hexanediol dimethacrylate, 1,9-hexanediol dimethacrylate, 1,10-hexanediol dimethacrylate, 1,11-hexanediol dimethacrylate, 1,12-hexanediol dimethacrylate, 1,13-hexanediol dimethacrylate, 1,14-hexanediol dimethacrylate, 1,15-hexanediol dimethacrylate, 1,16-hexanediol dimethacrylate, 1,17-hexanediol dimethacrylate, 1,18-hexanediol dimethacrylate, 1,19-hexanediol dimethacrylate, 1,20-hexanediol dimethacrylate, 1,21-hexanediol dimethacrylate, 1,22-hexanediol dimethacrylate, 1,23-hexanediol dimethacrylate, 1,24-hexanediol dimethacrylate, 1,25-hexanediol dimethacrylate, 1,30-hexanediol dimeth6-Hexanediol dimethacrylate, neopentyl glycol dimethacrylate, neopentyl glycol hydroxypivalate diacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dimethacrylate phosphate, polyethylene glycol diacrylate, polypropylene glycol diacrylate, tetraethylene glycol diacrylate, tetrabromobisphenol A diacrylate, triethylene glycol divinyl ether, triglycerol diacrylate, trimethylolpropane triacrylate, tripropylene glycol diacrylate, tris(acryloxyethyl)isobutyl cyanurate, phosphate triacrylate, phosphate diacrylate, acrylic acid propargyl ester, vinyl terminated polydimethylsiloxane, vinyl terminated diphenylsiloxane-dimethylsiloxane copolymer, vinyl terminated polyphenylmethylsiloxane, vinyl terminated trifluoromethylsiloxane-dimethylsiloxane copolymer, vinyl terminated diethylsiloxane-dimethylsiloxane copolymer, vinylmethylsiloxane, monomethacryloyloxypropyl terminated polydimethylsiloxane, monovinyl terminated polydimethylsiloxane, monoallyl-monotrimethylsiloxy terminated polyethylene oxide, and combinations thereof.

[0137] In some embodiments, the UV curable resin is a mercapto-functional compound that can crosslink with isocyanate, epoxy, or unsaturated compounds under UV curing conditions. In some embodiments, the polythiol is selected from the group consisting of pentaerythritol tetra(3-mercapto-propionate) (PETMP); trimethylol-propane tri(3-mercapto-propionate) (TMPMP); glycol di(3-mercapto-propionate) (GDMP); tris[25-(3-mercapto-propionyloxy)ethyl]isocyanurate (TEMPIC); di-pentaerythritol hexa(3-mercapto-propionate) (TEMPIC); ethoxylated trimethylolpropane tri(3-mercapto-propionate) (ETTMP1300 and ETTMP700); polycaprolactone tetra(3-mercapto-propionate) (PCL4MP1350); pentaerythritol tetramercaptoacetate (PETMA); trimethylol-propane trimercaptoacetate (TMPMA); or glycol dimercaptoacetate (GDMA). These compounds are sold under the trade name THIOCURE® by Bruno Bock (Marschacht, Germany).

[0138] In some embodiments, the UV curable resin is a polythiol. In some embodiments, the UV curable resin is a polythiol selected from the group consisting of ethylene glycol bis(thioglycolate), ethylene glycol bis(3-mercaptopropionate), trimethylolpropane tris(thioglycolate), trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(thioglycolate), pentaerythritol tetrakis(3-mercaptopropionate) (PETMP), and combinations thereof. In some embodiments, the UV curable resin is PETMP.

[0139] In some embodiments, the UV curable resin is a thiol-ene formulation that includes a polythiol and 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (TTT). In some embodiments, the UV curable resin is a thiol-ene formulation that includes PETMP and TTT.

[0140] In some embodiments, the UV-curable resin further comprises a photoinitiator. The photoinitiator initiates a crosslinking and / or curing reaction of the photosensitive material during exposure to light. In some embodiments, the photoinitiator is an acetophenone-based, benzoin-based, or thioxatenon-based.

[0141] In some embodiments, the photopolymerization initiator is a vinyl acrylate resin. In some embodiments, the photopolymerization initiator is MINS-311RM (Minuta Technology Co., Ltd, Korea).

[0142] In some embodiments, the photoinitiator is IRGACURE® 127, IRGACURE® 184, IRGACURE® 184D, IRGACURE® 2022, IRGACURE® 2100, IRGACURE® 250, IRGACURE® 270, IRGACURE® 2959, IRGACURE® 369, IRGACURE® 369 EG, IRGACURE® 379, IRGACURE® 500, IRGACURE® 651, IRGACURE® 754, IRGACURE® 784, IRGACURE® 819, IRGACURE® 819Dw, IRGACURE® 907, IRGACURE® 907R, IRGACURE® 907S, IRGACURE® 907T, IRGACURE® 907U, IRGACURE® 907R, IRGACURE® 907U ... FF, IRGACURE® Oxe01, IRGACURE® TPO-L, IRGACURE® 1173, IRGACURE® 1173D, IRGACURE® 4265, IRGACURE® BP, or IRGACURE® MBF (BASF Corporation, Wyandotte, Mich.). In some embodiments, the photoinitiator is TPO (2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide) or MBF (methylbenzoyl formate).

[0143] In some embodiments, the weight percentage of the at least one organic resin in the nanostructure composition is from about 5% to about 99%, from about 5% to about 95%, from about 5% to about 90%, from about 5% to about 80%, from about 5% to about 70%, from about 5% to about 60%, from about 5% to about 50%, from about 5% to about 40%, from about 5% to about 30%, from about 5% to about 20%, from about 5% to about 10%, from about 10% to about 99%, from about 10% to about 95%, from about 10% to about 90%, About 10% to about 80%, about 10% to about 70%, about 10% to about 60%, about 10% to about 50%, about 10% to about 40%, about 10% to about 30%, about 10% to about 20%, about 20% to about 99%, about 20% to about 95%, about 20% to about 90%, about 20% to about 80%, about 20% to about 70%, about 20% to about 60%, about 20% to about 50%, about 20% to about 40%, about 20% to about 30%, about 30% to about 99%, about 30% to About 95%, about 30% to about 90%, about 30% to about 80%, about 30% to about 70%, about 30% to about 60%, about 30% to about 50%, about 30% to about 40%, about 40% to about 99%, about 40% to about 95%, about 40% to about 90%, about 40% to about 80%, about 40% to about 70%, about 40% to about 60%, about 40% to about 50%, about 50% to about 99%, about 50% to about 95%, about 50% to about 90%, about 50% to about 80%, about 50% to about 70%, about 50% to about 60%, about 60% to about 99%, about 60% to about 95%, about 60% to about 90%, about 60% to about 80%, about 60% to about 70%, about 70% to about 99%, about 70% to about 95%, about 70% to about 90%, about 70% to about 80%, about 80% to about 99%, about 80% to about 95%, about 80% to about 90%, about 90% to about 99%, about 90% to about 95%, or about 95% to about 99%.

[0144] Method for preparing AIGS nanostructured compositions The present disclosure relates to (a) providing at least one AIGS nanostructure; (b) combining at least one organic resin with the composition of (a); A method for preparing a nanostructure composition is provided, comprising:

[0145] In some embodiments, the nanostructures have a PWL of 480-545 nm and at least about 80% of the emission is band-edge emission. In some embodiments, at least 80% of the emission is band-edge emission. In other embodiments, at least 90% of the emission is band-edge emission. In other embodiments, at least 95% of the emission is band-edge emission. In some embodiments, 92-98% of the emission is band-edge emission. In some embodiments, 93-96% of the emission is band-edge emission.

[0146] The present disclosure relates to (a) providing at least one population of AIGS nanostructures, the nanostructures being prepared using GaX3 (X=F, Cl, or Br) precursors and oxygen-free ligands, one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof; (b) combining at least one organic resin with the composition of (a); Also provided is a method for preparing a nanostructure composition, comprising:

[0147] In some embodiments, the nanostructures have a PWL between 480 and 545 nm, with at least about 60% of the emission being band edge emission.

[0148] The present disclosure relates to (a) providing at least one population of AIGS nanostructures, the nanostructures having a PWL between 480 and 545 nm, at least about 80% of the emission being band edge emission, and the nanostructures exhibiting a QY between 80 and 99%; (b) combining at least one organic resin with the composition of (a); Also provided is a method for preparing a nanostructure composition, comprising:

[0149] In some embodiments, the at least one population of nanostructures is rotated at a speed between about 100 rpm and about 10,000 rpm, between about 100 rpm and about 5,000 rpm, between about 100 rpm and about 3,000 rpm, between about 100 rpm and about 1,000 rpm, between about 100 rpm and about 500 rpm, between about 500 rpm and about 10,000 rpm, between about 500 rpm and about 5,000 rpm, between about 500 rpm and about 3,000 rpm. rpm, about 500 rpm to about 1,000 rpm, about 1,000 rpm to about 10,000 rpm, about 1,000 rpm to about 5,000 rpm, about 1,000 rpm to about 3,000 rpm, about 3,000 rpm to about 10,000 rpm, about 3,000 rpm to about 10,000 rpm, or about 5,000 rpm to about 10,000 rpm.

[0150] In some embodiments, at least one population of nanostructures is incubated for about 10 minutes to about 24 hours, about 10 minutes to about 20 hours, about 10 minutes to about 15 hours, about 10 minutes to about 10 hours, about 10 minutes to about 5 hours, about 10 minutes to about 1 hour, about 10 minutes to about 30 minutes, about 30 minutes to about 24 hours, about 30 minutes to about 20 hours, about 30 minutes to about 15 hours, about 30 minutes to about 10 hours, about 30 minutes to about 5 hours, about 30 minutes to about 1 hour, about 1 hour to about 24 hours, about It is mixed with at least one organic resin for a period of 1 hour to about 20 hours, about 1 hour to about 15 hours, about 1 hour to about 10 hours, about 1 hour to about 5 hours, about 5 hours to about 24 hours, about 5 hours to about 20 hours, about 5 hours to about 15 hours, about 5 hours to about 10 hours, about 10 hours to about 24 hours, about 10 hours to about 20 hours, about 10 hours to about 15 hours, about 15 hours to about 24 hours, about 15 hours to about 20 hours, or about 20 hours to about 24 hours.

[0151] In some embodiments, the at least one population of nanostructures is admixed with the at least one organic resin at a temperature of about -5°C to about 100°C, about -5°C to about 75°C, about -5°C to about 50°C, about -5°C to about 23°C, about 23°C to about 100°C, about 23°C to about 75°C, about 23°C to about 50°C, about 50°C to about 100°C, about 50°C to about 75°C, or about 75°C to about 100°C. In some embodiments, the at least one organic resin is admixed with the at least one population of nanostructures at a temperature of about 23°C to about 50°C.

[0152] In some embodiments, when two or more organic resins are used, the organic resins are added and mixed together. In some embodiments, the first organic resin is mixed at about 100 rpm to about 10,000 rpm, about 100 rpm to about 5,000 rpm, about 100 rpm to about 3,000 rpm, about 100 rpm to about 1,000 rpm, about 100 rpm to about 500 rpm, about 500 rpm to about 10,000 rpm, about 500 rpm to about 5,000 rpm, about 500 rpm to about 3,000 rpm. The second organic resin is mixed with the second organic resin at a stirring speed of about 500 rpm to about 1,000 rpm, about 1,000 rpm to about 10,000 rpm, about 1,000 rpm to about 5,000 rpm, about 1,000 rpm to about 3,000 rpm, about 3,000 rpm to about 10,000 rpm, about 3,000 rpm to about 10,000 rpm, or about 5,000 rpm to about 10,000 rpm.

[0153] In some embodiments, the first organic resin is reacted with the first organic resin for about 10 minutes to about 24 hours, about 10 minutes to about 20 hours, about 10 minutes to about 15 hours, about 10 minutes to about 10 hours, about 10 minutes to about 5 hours, about 10 minutes to about 1 hour, about 10 minutes to about 30 minutes, about 30 minutes to about 24 hours, about 30 minutes to about 20 hours, about 30 minutes to about 15 hours, about 30 minutes to about 10 hours, about 30 minutes to about 5 hours, about 30 minutes to about 1 hour, about 1 hour to about 24 hours, or about 1 hour. The second organic resin is mixed with the second organic resin for a period of about 1 hour to about 20 hours, about 1 hour to about 15 hours, about 1 hour to about 10 hours, about 1 hour to about 5 hours, about 5 hours to about 24 hours, about 5 hours to about 20 hours, about 5 hours to about 15 hours, about 5 hours to about 10 hours, about 10 hours to about 24 hours, about 10 hours to about 20 hours, about 10 hours to about 15 hours, about 15 hours to about 24 hours, about 15 hours to about 20 hours, or about 20 hours to about 24 hours.

[0154] Characteristics of AIGS nanostructures In some embodiments, the AIGS nanostructures exhibit high photoluminescence quantum yields, such as from about 50% to about 99%, from about 50% to about 95%, from about 50% to about 90%, from about 50% to about 85%, from about 50% to about 80%, from about 50% to about 70%, from about 50% to about 60%, from 60% to about 99%, from about 60% to about 95%, from about 60% to about 90%, from about 60% to about 85%, from about 60% to about 80%, from about 60% to about 70%, from about 70% to about 99%, from about 70% to about 95%, The nanostructures exhibit a photoluminescence quantum yield of about 70% to about 90%, about 70% to about 85%, about 70% to about 80%, about 80% to about 99%, about 80% to about 95%, about 80% to about 90%, about 80% to about 85%, about 85% to about 99%, about 85% to about 95%, about 80% to about 85%, about 85% to about 99%, about 85% to about 90%, about 90% to about 99%, about 90% to about 95%, or about 95% to about 99%. In some embodiments, the nanostructures exhibit a photoluminescence quantum yield of about 82% to about 96%, about 85% to about 96%, and about 93% to about 94%.

[0155] The photoluminescence spectrum of the nanostructure can cover a wide desired portion of the spectrum. In some embodiments, the photoluminescence spectrum of the nanostructure has an emission maximum of 300 nm to 750 nm, 300 nm to 650 nm, 300 nm to 550 nm, 300 nm to 450 nm, 450 nm to 750 nm, 450 nm to 650 nm, 450 nm to 550 nm, 450 nm to 750 nm, 450 nm to 650 nm, 450 nm to 550 nm, 550 nm to 750 nm, 550 nm to 650 nm, or 650 nm to 750 nm. In some embodiments, the photoluminescence spectrum of the nanostructure has an emission maximum of 450 nm to 550 nm.

[0156] The size distribution of the nanostructures can be relatively narrow. In some embodiments, the photoluminescence spectrum of the population of nanostructures can have a full width at half maximum of 10 nm to 60 nm, 10 nm to 40 nm, 10 nm to 30 nm, 10 nm to 20 nm, 20 nm to 60 nm, 20 nm to 40 nm, 20 nm to 30 nm, 25 nm to 60 nm, 25 nm to 40 nm, 25 nm to 30 nm, 30 nm to 60 nm, 30 nm to 40 nm, or 40 nm to 60 nm. In some embodiments, the photoluminescence spectrum of the population of nanostructures can have a full width at half maximum of 24 nm to 50 nm, 24 to 28 nm, 27 to 32 nm, or 29 to 38 nm.

[0157] In some embodiments, the nanostructure emits light having a peak emission wavelength (PWL) of about 400 nm to about 650 nm, about 400 nm to about 600 nm, about 400 nm to about 550 nm, about 400 nm to about 500 nm, about 400 nm to about 450 nm, about 450 nm to about 650 nm, about 450 nm to about 600 nm, about 450 nm to about 550 nm, about 450 nm to about 500 nm, about 500 nm to about 650 nm, about 500 nm to about 600 nm, about 500 nm to about 550 nm, about 550 nm to about 650 nm, about 550 nm to about 600 nm, or about 600 nm to about 650 nm. In some embodiments, the nanostructure emits light having a PWL of about 500 nm to about 550 nm.

[0158] The optical density at 450 nm (OD ) per unit mass is used as a predictor of blue light absorption efficiency. 450 The optical density at 450 nm (OD / mass) can be calculated by measuring the optical density of the nanostructure solution in a 1 cm pathlength cuvette and dividing by the dry mass per mL of the same solution after removing all volatiles under vacuum (<200 mTorr). In some embodiments, the nanostructures have an optical density at 450 nm (OD) per mass of about 0.28 / mg to about 0.5 / mg, about 0.28 / mg to about 0.4 / mg, about 0.28 / mg to about 0.35 / mg, about 0.28 / mg to about 0.32 / mg, about 0.32 / mg to about 0.5 / mg, about 0.32 / mg to about 0.4 / mg, about 0.32 / mg to about 0.35 / mg, about 0.35 / mg to about 0.5 / mg, about 0.35 / mg to about 0.4 / mg, or about 0.4 / mg to about 0.5 / mg. 450 / mass).

[0159] film The nanostructures of the present invention can be embedded in a polymer matrix using any suitable method. As used herein, the term "embedded" is used to indicate that the nanostructures are surrounded or enveloped by the polymer that constitutes the majority of the matrix's components. In some embodiments, the at least one nanostructure population is suitably uniformly distributed throughout the matrix. In some embodiments, the at least one nanostructure population is distributed according to an application-specific distribution. In some embodiments, the nanostructures are mixed into a polymer and applied to the surface of a material.

[0160] In some embodiments, the present disclosure provides: (a) a composition comprising at least one population of AIGS nanostructures, one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof, and at least one ligand bound to the nanostructures; (b) at least one organic resin; A nanostructured film layer is provided comprising:

[0161] In some embodiments, a portion of the ligands are bound to the nanostructures, hi other embodiments, the nanostructure surface is saturated with the ligands.

[0162] In some embodiments, the nanostructures have a PWL of 480-545 nm.

[0163] The present disclosure relates to (a) providing at least one population of AIGS nanostructures and one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof; (b) combining at least one organic resin with the composition of (a); Also provided is a method for preparing a nanostructured film layer, comprising:

[0164] In some embodiments, the nanostructures have a PWL of 480-545 nm.

[0165] In some embodiments, at least 80% of the emission is band-edge emission. In other embodiments, at least 90% of the emission is band-edge emission. In other embodiments, at least 95% of the emission is band-edge emission. In some embodiments, 92-98% of the emission is band-edge emission. In some embodiments, 93-96% of the emission is band-edge emission.

[0166] Ligands and Additives In some embodiments, the nanostructure composition further comprises an amino ligand having formula I: [ka] During the ceremony, x is 1 to 100; y is 0 to 100, and R 2 is C 1~20 The present invention further includes amino ligands having a substituent (wherein the substituent is alkyl).

[0167] In some embodiments, x is 1 to 100, 1 to 50, 1 to 20, 1 to 10, 1 to 5, 5 to 100, 5 to 50, 5 to 20, 5 to 10, 10 to 100, 10 to 50, 10 to 20, 20 to 100, 20 to 50, or 50 to 100. In some embodiments, x is 10 to 50. In some embodiments, x is 10 to 20. In some embodiments, x is 1. In some embodiments, x is 19. In some embodiments, x is 6. In some embodiments, x is 10.

[0168] In some embodiments, R 2 is C 1~20 In some embodiments, R 2 is C 1~10 In some embodiments, R 2 is C 1~5 In some embodiments, R 2 is -CH2CH3.

[0169] In some embodiments, the compound of formula I is an amine-terminated polymer commercially available from Huntsman Petrochemical Corporation. In some embodiments, the amine-terminated polymer of formula (VI) has x=1, y=9, and R 2 = -CH3 and JEFFAMINE M-600 (Huntsman Petrochemical Corporation, Texas). JEFFAMINE M-600 has a molecular weight of about 600. In some embodiments, the amine-terminated polymer of formula (III) has x = 19, y = 3, and R 2 = -CH3 and JEFFAMINE M-1000 (Huntsman Petrochemical Corporation, Texas). JEFFAMINE M-1000 has a molecular weight of about 1,000. In some embodiments, the amine-terminated polymer of formula (III) has x = 6, y = 29, and R 2 = -CH3 and JEFFAMINE M-2005 (Huntsman Petrochemical Corporation, Texas). JEFFAMINE M-2005 has a molecular weight of about 2,000. In some embodiments, the amine-terminated polymer of formula (III) has x = 31, y = 10, and R 2 =-CH3 and JEFFAMINE M-2070 (Huntsman Petrochemical Corporation, Texas). JEFFAMINE M-2070 has a molecular weight of about 2,000. In another embodiment, the ligand is a polyethylene glycol amine available from CreativePEGWorks, such as PEG550-amine and PEG350-amine.

[0170] In some embodiments, the ligand is a sterically hindered phenol having formula II: [ka] In the formula, R 3 and R4 is a C3-6 secondary or tertiary alkyl group, R 5 is hydrogen or an optionally substituted C1-6 alkyl group. In some embodiments, R3 and R4 are isopropyl, 2-butyl, 2-pentyl, 3-pentyl, 2-hexyl, 3-hexyl, t-butyl, 2-methyl-2-pentyl, or 3-methyl-3-pentyl. In some embodiments, R 5 is at the 3- or 4-position of formula II.

[0171] R 5 C 1~6 Optional substituents on the alkyl group include nitro, haloalkoxy, aryloxy, aralkyloxy, alkylthio, sulfonamido, alkylcarbonyl, arylcarbonyl, alkylsulfonyl, arylsulfonyl, ureido, guanidino, carbamate, carboxy, alkoxycarbonyl, carboxyalkyl, or C(=O)R. 7 (In the formula, R 7 is an alkoxy group which may be further substituted by one or more other alkoxy groups).

[0172] In some embodiments, R 7 is expressed by the following formula: CH p (CH2-O-) 4-p where p is 0 to 3 and the oxygen atom is bonded to the carbonyl of formula II. 7 teeth, [ka] It is.

[0173] In some embodiments, R 7 teeth, [ka] and formula II is [ka] where R 7 The oxygen atom in * is attached to the carbonyl of formula II at the position shown.

[0174] In some embodiments, the compound of formula II is pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] or 2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diylbis(2-methylpropane-2,1-diyl)bis[3-[3-(tert-butyl)-4-hydroxy-5-methylphenyl]propanoate].

[0175] The ligands having formula II bind to the nanostructures and also act as antioxidants in nanostructure compositions such as inks and films. In addition, because the ligands are sterically hindered, they reduce the free volume at the nanostructure surface, thereby reducing or preventing oxidation by ambient oxygen and improving air stability.

[0176] In some embodiments, the nanostructure film layer is a color conversion layer.

[0177] The nanostructure composition can be deposited by any suitable method known in the art, including, but not limited to, painting, spray coating, solvent spray, wet coating, adhesive coating, spin coating, tape coating, roll coating, flow coating, inkjet vapor jetting, drop casting, blade coating, mist deposition, or combinations thereof. In some embodiments, the nanostructure composition is cured after deposition. Suitable curing methods include photocuring, such as UV curing, and thermal curing. Conventional lamination film processing, tape coating, and / or roll-to-roll manufacturing methods can be employed to form the nanostructured film of the present invention. The nanostructure composition can be coated directly onto the desired layer of the substrate. Alternatively, the nanostructure composition can be formed into a solid layer as a separate element and then applied to the substrate. In some embodiments, the nanostructure composition can be deposited onto one or more barrier layers.

[0178] Metal Alkoxide Metal alkoxides have the general formula M(OR) x where R is a straight chain, branched chain, or cyclic alkyl, typically containing 1 to 10 carbon atoms, and x is the valence of the metal. In some embodiments, metal alkoxides include metal methoxides, metal ethoxides, metal n-propoxides, metal isopropoxides, metal n-butoxides, metal isobutoxides, metal n-pentoxides, metal isopentoxides, metal n-hexoxides, metal isohexoxides, metal n-heptoxides, metal isoheptoxides, metal n-octoxides, metal n-isooctoxides, metal n-nonoxides, metal n-isononoxides, metal n-decyloxides, and metal n-isodecyloxides.

[0179] In some embodiments, the metal of the metal alkoxide may include one or more of lithium, sodium, potassium, rubidium, cesium, beryllium, magnesium, calcium, strontium, barium, scandium, yttrium, lutetium, lanthanum, cerium, praseodymium, neodymium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, titanium, zirconium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, manganese, rhenium, iron, ruthenium, osmium, cobalt, nickel, platinum, copper, zinc, cadmium, boron, aluminum, gallium, indium, thallium, silicon, germanium, tin, lead, arsenic, antimony, and bismuth. In some embodiments, metals include one or more of aluminum, antimony, arsenic, barium, bismuth, boron, cerium, gadolinium, gallium, germanium, hafnium, indium, iron, lanthanum, lithium, magnesium, molybdenum, neodymium, phosphorus, silicon, sodium, strontium, tantalum, thallium, tin, titanium, tungsten, vanadium, yttrium, zinc, and zirconium.

[0180] In some embodiments, the metal alkoxide includes one or more of the Group 4 metals, including titanium, zirconium, and hafnium.

[0181] In some embodiments, the metal alkoxide is zirconium(IV) tetramethoxide, zirconium(IV) tetraethoxide, zirconium(IV) tetra-n-propoxide, zirconium(IV) tetra-isopropoxide, zirconium(IV) tetra-n-butoxide, zirconium(IV) tetra-isobutoxide, zirconium(IV) tetra-n-pentoxide, zirconium(IV) tetra-isopentoxide, zirconium(IV) tetra-n-hexoxide, zirconium(IV) ) at least one zirconium alkoxide including zirconium(IV) tetra-isohexoxide, zirconium(IV) tetra-heptoxide, zirconium(IV) tetra-isoheptoxide, zirconium(IV) tetra-n-octoxide, zirconium(IV) tetra-n-isooctoxide, zirconium(IV) tetra-n-nonoxide, zirconium(IV) tetra-n-isononoxide, zirconium(IV) tetra-n-decyloxide, and zirconium(IV) tetra-n-isodecyloxide.

[0182] In some embodiments, metal alkoxides can form a sol-gel around the AIGS nanostructures, thus forming an oxygen barrier and providing stabilization of the AIGS nanostructures. See Brinker and Scherer, (1990) Sol-Gel Science: The Physics and Chemistry of Sol-Gel Processing. Academic Press.

[0183] In some embodiments, the metal alkoxide is present in the AIGS film composition at least 0.005 wt% (50 ppm). In some embodiments, the metal oxide is present in the AIGS film composition in an amount of about 0.03 to about 3 wt%. In some embodiments, the metal oxide is present in the AIGS film composition in an amount of about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1.0, about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.6, about 2.7, about 2.8, about 2.9, or about 3 wt%.

[0184] Metal alkoxide hydrolysis products Metal alkoxide hydrolysis products have the general formula M(OH) x (OR) ywhere R is a straight chain, branched chain, or cyclic alkyl, typically containing 1 to 10 carbon atoms, and x+y is equal to the valence of the metal. Hydrolysis products of metal alkoxides include zirconium(IV) monohydroxide trimethoxide, zirconium(IV) dihydroxide dimethoxide, zirconium(IV) trihydroxide monomethoxide, zirconium(IV) tetrahydroxide, zirconium(IV) monohydroxide triethoxide, zirconium(IV) dihydroxide diethoxide, zirconium(IV) trihydroxide monoethoxide, zirconium(IV) monohydroxide tri-n-propoxide, zirconium(IV) dihydroxide trimeth ... Hydroxide di-n-propoxide, zirconium(IV) trihydroxide mono-n-propoxide, zirconium(IV) monohydroxide triisopropoxide, zirconium(IV) dihydroxide diisopropoxide, zirconium(IV) trihydroxide monoisopropoxide, zirconium(IV) monohydroxide tri-n-butoxide, zirconium(IV) dihydroxide di-n-butoxide, zirconium(IV) trihydroxide mono-n-butoxide, zirconium(IV) monohydroxide do triisobutoxide, zirconium(IV) dihydroxide diisobutoxide, zirconium(IV) trihydroxide monoisobutoxide, zirconium(IV) monohydroxide tri-n-pentoxide, zirconium(IV) dihydroxide di-n-pentoxide, zirconium(IV) trihydroxide mono-n-pentoxide, zirconium(IV) monohydroxide triisopentoxide, zirconium(IV) dihydroxide diisopentoxide, zirconium(IV) trihydroxide monoisopentoxide oxide, zirconium(IV) monohydroxide tri-n-hexoxide, zirconium(IV) dihydroxide di-n-hexoxide, zirconium(IV) trihydroxide mono-n-hexoxide, zirconium(IV) monohydroxide triisohexoxide, zirconium(IV) dihydroxide diisohexoxide, zirconium(IV) trihydroxide monoisohexoxide, zirconium(IV) monohydroxide tri-n-heptoxide, zirconium(IV) dihydroxide di-n-heptoxide,Zirconium(IV) trihydroxide mono-n-heptoxide, zirconium(IV) monohydroxide triisoheptoxide, zirconium(IV) dihydroxide diisoheptoxide, zirconium(IV) trihydroxide monoisoheptoxide, zirconium(IV) monohydroxide tri-n-octoxide, zirconium(IV) dihydroxide di-n-octoxide, zirconium(IV) trihydroxide mono-n-octoxide, zirconium(IV) monohydroxide tri-n-isooctoxide, zirconium(IV) di Hydroxide di-n-isooctoxide, zirconium(IV) trihydroxide mono-n-isooctoxide, zirconium(IV) monohydroxide tri-n-nonoxide, zirconium(IV) dihydroxide di-n-nonoxide, zirconium(IV) trihydroxide mono-n-nonoxide, zirconium(IV) monohydroxide tri-n-isononoxide, zirconium(IV) dihydroxide di-n-isononoxide, zirconium(IV) trihydroxide mono-n-isononoxide, zirconium(IV) monohydroxide tri -n-decyloxide, zirconium(IV) dihydroxide di-n-decyloxide, zirconium(IV) trihydroxide mono-n-decyloxide, zirconium(IV) monohydroxide tri-n-isodecyloxide, zirconium(IV) dihydroxide di-n-isodecyloxide, zirconium(IV) trihydroxide mono-n-isodecyloxide, titanium(IV) monohydroxide trimethoxide, titanium(IV) dihydroxide dimethoxide, titanium(IV) trihydroxide monomethoxide, titanium(IV) tetrahydroxide, titanium Titanium(IV) monohydroxide triethoxide, titanium(IV) dihydroxide diethoxide, titanium(IV) trihydroxide monoethoxide, titanium(IV) monohydroxide tri-n-propoxide, titanium(IV) dihydroxide di-n-propoxide, titanium(IV) trihydroxide mono-n-propoxide, titanium(IV) monohydroxide triisopropoxide, titanium(IV) dihydroxide diisopropoxide, titanium(IV) trihydroxide monoisopropoxide, titanium(IV) monohydroxide tri-n-butoxide,Titanium(IV) dihydroxide di-n-butoxide, titanium(IV) trihydroxide mono-n-butoxide, titanium(IV) monohydroxide triisobutoxide, titanium(IV) dihydroxide diisobutoxide, titanium(IV) trihydroxide monoisobutoxide, titanium(IV) monohydroxide tri-n-pentoxide, titanium(IV) dihydroxide di-n-pentoxide, titanium(IV) trihydroxide mono-n-pentoxide, titanium(IV) monohydroxide triisopentoxide, titanium(IV) dihydroxide diisopentoxide titanium(IV) trihydroxide monoisopentoxide, titanium(IV) monohydroxide tri-n-hexoxide, titanium(IV) dihydroxide di-n-hexoxide, titanium(IV) trihydroxide mono-n-hexoxide, titanium(IV) monohydroxide triisohexoxide, titanium(IV) dihydroxide diisohexoxide, titanium(IV) trihydroxide monoisohexoxide, titanium(IV) monohydroxide tri-n-heptoxide, titanium(IV) dihydroxide di-n-heptoxide, titanium(IV) trihydroxide Titanium(IV) hydroxide mono-n-heptoxide, titanium(IV) monohydroxide triisoheptoxide, titanium(IV) dihydroxide diisoheptoxide, titanium(IV) trihydroxide monoisoheptoxide, titanium(IV) monohydroxide tri-n-octoxide, titanium(IV) dihydroxide di-n-octoxide, titanium(IV) trihydroxide mono-n-octoxide, titanium(IV) monohydroxide tri-n-isooctoxide, titanium(IV) dihydroxide di-n-isooctoxide, titanium(IV) trihydroxide mono- n-isooctoxide, titanium(IV) monohydroxide tri-n-nonoxide, titanium(IV) dihydroxide di-n-nonoxide, titanium(IV) trihydroxide mono-n-nonoxide, titanium(IV) monohydroxide tri-n-isononoxide, titanium(IV) dihydroxide di-n-isononoxide, titanium(IV) trihydroxide mono-n-isononoxide, titanium(IV) monohydroxide tri-n-decyloxide, titanium(IV) dihydroxide di-n-decyloxide, titanium(IV) trihydroxide mono-n-decyloxide,Titanium(IV) monohydroxide tri-n-isodecyloxide, titanium(IV) dihydroxide di-n-isodecyloxide, titanium(IV) trihydroxide mono-n-isodecyloxide, hafnium(IV) monohydroxide trimethoxide, hafnium(IV) dihydroxide dimethoxide, hafnium(IV) trihydroxide monomethoxide, hafnium(IV) tetrahydroxide, hafnium(IV) monohydroxide triethoxide, hafnium(IV) dihydroxide diethoxide, hafnium(IV) trihydroxide monoethoxide , hafnium(IV) monohydroxide tri-n-propoxide, hafnium(IV) dihydroxide di-n-propoxide, hafnium(IV) trihydroxide mono-n-propoxide, hafnium(IV) monohydroxide triisopropoxide, hafnium(IV) dihydroxide diisopropoxide, hafnium(IV) trihydroxide monoisopropoxide, hafnium(IV) monohydroxide tri-n-butoxide, hafnium(IV) dihydroxide di-n-butoxide, hafnium(IV) trihydroxide mono-n-butoxide , hafnium(IV) monohydroxide triisobutoxide, hafnium(IV) dihydroxide diisobutoxide, hafnium(IV) trihydroxide monoisobutoxide, hafnium(IV) monohydroxide tri-n-pentoxide, hafnium(IV) dihydroxide di-n-pentoxide, hafnium(IV) trihydroxide mono-n-pentoxide, hafnium(IV) monohydroxide triisopentoxide, hafnium(IV) dihydroxide diisopentoxide, hafnium(IV) trihydroxide monoisopentoxide, haf hafnium(IV) monohydroxide tri-n-hexoxide, hafnium(IV) dihydroxide di-n-hexoxide, hafnium(IV) trihydroxide mono-n-hexoxide, hafnium(IV) monohydroxide triisohexoxide, hafnium(IV) dihydroxide diisohexoxide, hafnium(IV) trihydroxide monoisohexoxide, hafnium(IV) monohydroxide tri-n-heptoxide, hafnium(IV) dihydroxide di-n-heptoxide, hafnium(IV) trihydroxide mono-n-heptoxide,Hafnium(IV) monohydroxide triisoheptoxide, hafnium(IV) dihydroxide diisoheptoxide, hafnium(IV) trihydroxide monoisoheptoxide, hafnium(IV) monohydroxide tri-n-octoxide, hafnium(IV) dihydroxide di-n-octoxide, hafnium(IV) trihydroxide mono-n-octoxide, hafnium(IV) monohydroxide tri-n-isooctoxide, hafnium(IV) dihydroxide di-n-isooctoxide, hafnium(IV) trihydroxide mono-n-isooctoxide, hafnium(IV) monohydroxide tri-n-nonoxide, hafnium(IV) dihydroxide di-n- nonoxide, hafnium(IV) trihydroxide mono-n-nonoxide, hafnium(IV) monohydroxide tri-n-isononoxide, hafnium(IV) dihydroxide di-n-isononoxide, hafnium(IV) trihydroxide mono-n-isononoxide, hafnium(IV) monohydroxide tri-n-decyloxide, hafnium(IV) dihydroxide di-n-decyloxide, hafnium(IV) trihydroxide mono-n-decyloxide, hafnium(IV) monohydroxide tri-n-isodecyloxide, hafnium(IV) dihydroxide di-n-isodecyloxide, and hafnium(IV) trihydroxide mono-n-isodecyloxide.

[0185] In some embodiments, the metal alkoxide hydrolysis product is present in the AIGS film composition at at least 0.005 wt.% (50 ppm). In some embodiments, the metal oxide hydrolysis product is present in the AIGS film composition in an amount of about 0.03 to about 3 wt.%. In some embodiments, the metal oxide hydrolysis product is present in the AIGS film composition in an amount of about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1.0, about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.6, about 2.7, about 2.8, about 2.9, or about 3 wt.%.

[0186] Metal Halides Metal halides have the general formula MX y where y is the valence of the metal. Metal halides include zirconium(IV) tetrafluoride, zirconium(IV) tetrachloride, zirconium(IV) tetrabromide, zirconium(IV) tetraiodide, titanium(IV) tetrafluoride, titanium(IV) tetrachloride, titanium(IV) tetrabromide, titanium(IV) tetraiodide, hafnium(IV) tetrafluoride, hafnium(IV) tetrachloride, hafnium(IV) tetrabromide, hafnium(IV) tetraiodide, gallium(III) trifluoride, gallium(III) trichloride, gallium(III) tribromide, and gallium(III) triiodide.

[0187] In some embodiments, the metal halide is present in the AIGS film composition at least 0.005 wt% (50 ppm). In some embodiments, the metal halide is present in the AIGS film composition in an amount of about 0.03 to about 3 wt%. In some embodiments, the metal halide is present in the AIGS film composition in an amount of about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1.0, about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.6, about 2.7, about 2.8, about 2.9, or about 3 wt%.

[0188] Metal halide hydrolysis products The metal halide hydrolysis products have the general formula MX y (OH) xwhere x+y is equal to the valence of the metal. Metal halide hydrolysis products include zirconium(IV) monohydroxide trichloride, zirconium(IV) dihydroxide difluoride, zirconium(IV) trihydroxide monofluoride, zirconium(IV) tetrahydroxide, titanium(IV) monohydroxide trifluoride, titanium(IV) dihydroxide difluoride, titanium(IV) trihydroxide monofluoride, titanium(IV) tetrahydroxide, titanium(IV) monohydroxide trifluoride, titanium(IV) dihydroxide difluoride, Titanium(IV) trihydroxide monofluoride, titanium(IV) tetrahydroxide, hafnium(IV) monohydroxide trifluoride, hafnium(IV) dihydroxide difluoride, hafnium(IV) trihydroxide monofluoride, hafnium(IV) tetrahydroxide, zirconium(IV) monohydroxide trichloride, zirconium(IV) dihydroxide dichloride, zirconium(IV) trihydroxide monochloride, zirconium(IV) tetrahydroxide, titanium(IV) monohydroxide trichloride hydride, titanium(IV) dihydroxide dichloride, titanium(IV) trihydroxide monochloride, titanium(IV) tetrahydroxide, titanium(IV) monohydroxide trichloride, titanium(IV) dihydroxide dichloride, titanium(IV) trihydroxide monochloride, titanium(IV) tetrahydroxide, hafnium(IV) monohydroxide trichloride, hafnium(IV) dihydroxide dichloride, hafnium(IV) trihydroxide monochloride, hafnium(IV) tetrahydroxide, zirconium(IV) monohydroxide titanium(IV) monohydroxide tribromide, titanium(IV) dihydroxide dibromide, titanium(IV) trihydroxide monobromide, titanium(IV) tetrahydroxide, titanium(IV) monohydroxide tribromide, titanium(IV) dihydroxide dibromide, titanium(IV) trihydroxide monobromide, titanium(IV) tetrahydroxide, titanium(IV) monohydroxide tribromide, titanium(IV) dihydroxide dibromide, titanium(IV) trihydroxide monobromide, titanium(IV) tetrahydroxide,hafnium(IV) monohydroxide tribromide, hafnium(IV) dihydroxide dibromide, hafnium(IV) trihydroxide monobromide, hafnium(IV) tetrahydroxide, zirconium(IV) monohydroxide triiodide, zirconium(IV) dihydroxide diiodide, zirconium(IV) trihydroxide monoiodide, zirconium(IV) tetrahydroxide, titanium(IV) monohydroxide triiodide, titanium(IV) dihydroxide diiodide, titanium(IV) trihydroxide monoiodide, titanium(IV) tetrahydroxide, titanium(IV) monohydroxide triiodide, titanium(IV) dihydroxide diiodide, titanium(IV) trihydroxide monoiodide, titanium(IV) tetrahydroxide, hafnium(IV) monohydroxide triiodide, hafnium(IV) dihydroxide diiodide, hafnium(IV) trihydroxide monoiodide, and hafnium(IV) tetrahydroxide. ,

[0189] In some embodiments, the metal halide hydrolysis product is present in the AIGS film composition at least 0.005 wt% (50 ppm). In some embodiments, the metal oxide is present in the AIGS film composition in an amount of about 0.03 to about 3 wt%. In some embodiments, the metal halide hydrolysis product is present in the film composition in an amount of about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1.0, about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.6, about 2.7, about 2.8, about 2.9, or about 3 wt%.

[0190] organometallic compound Organometallic compounds contain a metal-carbon bond and have the formula R xM, where R is a straight chain, branched chain, or cyclic alkyl, typically containing 1 to 10 carbon atoms, and x is the valence of the metal. Examples of the organometallic compounds include tetramethylzirconium, tetraethylzirconium, tetra-n-propylzirconium, tetraisopropylzirconium, tetra-n-butylzirconium, tetraisobutylzirconium, tetra-n-pentylzirconium, tetraisopentylzirconium, tetra-n-hexylzirconium, tetraisohexylzirconium, tetra-n-heptylzirconium, tetraisoheptylzirconium, tetra-n-octylzirconium, tetra-n-isooctylzirconium, tetra-n-nonylzirconium, tetra-n-isononylzirconium, tetra-n-decylzirconium, tetra-n-isodecylzirconium, tetramethyltitanium, tetraethyltitanium, tetra-n-propyltitanium, tetraisopropyltitanium, tetra-n-butyltitanium, tetraisobutyltitanium, tetra-n-pentyltitanium, tetraisopentyltitanium, tetra-n-hexyl titanium, tetraisohexyl titanium, tetra-n-heptyl titanium, tetraisoheptyl titanium, tetra-n-octyl titanium, tetra-n-isooctyl titanium, tetra-n-nonyl titanium, tetra-n-isononyl titanium, tetra-n-decyl titanium, tetra-n-isodecyl titanium, tetramethyl hafnium, tetraethyl hafnium, tetra-n-propyl hafnium, tetraisopropyl hafnium, tetra-n-butyl hafnium, tetraisobutyric acid tetra-n-pentylhafnium, tetra-n-pentylhafnium, tetra-n-hexylhafnium, tetra-n-isohexylhafnium, tetra-n-heptylhafnium, tetra-n-isoheptylhafnium, tetra-n-octylhafnium, tetra-n-isooctylhafnium, tetra-n-nonylhafnium, tetra-n-isononylhafnium, tetra-n-decylhafnium, and tetra-n-isodecylhafnium.

[0191] In some embodiments, the organometallic compound is present in the AIGS film composition at least 0.005 wt% (50 ppm). In some embodiments, the organometallic compound is present in the AIGS film composition in an amount of about 0.03 to about 3 wt%. In some embodiments, the organometallic compound is present in the AIGS film composition in an amount of about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1.0, about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.6, about 2.7, about 2.8, about 2.9, or about 3 wt%.

[0192] organometallic hydrolyzed compounds The organometallic hydrolysis products have the formula R x M(OH) ywhere R is a straight chain, branched chain, or cyclic alkyl, typically containing 1 to 10 carbon atoms, and x+y is equal to the valence of the metal. The organometallic hydrolysis products include trimethyl zirconium monohydroxide, triethyl zirconium monohydroxide, tri-n-propyl zirconium monohydroxide, triisopropyl zirconium monohydroxide, tri-n-butyl zirconium monohydroxide, triisobutyl zirconium monohydroxide, tri-n-pentyl zirconium monohydroxide, triisopentyl zirconium monohydroxide, tri-n-hexyl zirconium monohydroxide, triisohexyl zirconium monohydroxide, tri-n-heptyl zirconium monohydroxide, triisoheptyl zirconium monohydroxide, tri-n-octyl zirconium monohydroxide, tri-n-isooctyl zirconium monohydroxide, tri-n-nonyl zirconium monohydroxide, tri-n-isononyl zirconium monohydroxide, tri-n-decyl zirconium monohydroxide, tri-n-isodecyl zirconium monohydroxide, trimethyl titanium monohydroxide, triethyl titanium monohydroxide, titanium monohydroxide, tri-n-propyl titanium monohydroxide, triisopropyl titanium monohydroxide, tri-n-butyl titanium monohydroxide, triisobutyl titanium monohydroxide, tri-n-pentyl titanium monohydroxide, triisopentyl titanium monohydroxide, tri-n-hexyl titanium monohydroxide, triisohexyl titanium monohydroxide, tri-n-heptyl titanium monohydroxide, triisoheptyl titanium monohydroxide, tri-n-octyl titanium monohydroxide, tri-n-isooctyl titanium monohydroxide, tri-n-nonyl titanium monohydroxide, tri-n-isononyl titanium monohydroxide, tri-n-decyl titanium monohydroxide, tri-n-isodecyl titanium monohydroxide, trimethyl hafnium monohydroxide, triethyl hafnium monohydroxide, tri-n-propyl hafnium monohydroxide, triisopropyl hafnium monohydroxide, tri-n-butyl hafnium monohydroxide, triisobutyl hafnium monohydroxide,Tri-n-pentylhafnium monohydroxide, triisopentylhafnium monohydroxide, tri-n-hexylhafnium monohydroxide, triisohexylhafnium monohydroxide, tri-n-heptylhafnium monohydroxide, triisoheptylhafnium monohydroxide, tri-n-octylhafnium monohydroxide, tri-n-isooctylhafnium monohydroxide, tri-n-nonylhafnium monohydroxide, tri-n-isononylhafnium monohydroxide, tri-n-decylhafnium monohydroxide hafnium monohydroxide, tri-n-isodecyl hafnium monohydroxide, dimethyl zirconium dihydroxide, diethyl zirconium dihydroxide, di-n-propyl zirconium dihydroxide, diisopropyl zirconium dihydroxide, di-n-butyl zirconium dihydroxide, diisobutyl zirconium dihydroxide, di-n-pentyl zirconium dihydroxide, diisopentyl zirconium dihydroxide, di-n-hexyl zirconium dihydroxide, diisohexyl zirconium dihydroxide, di-n-heptyl zirconium titanium dihydroxide, diisoheptylzirconium dihydroxide, di-n-octylzirconium dihydroxide, di-n-isooctylzirconium dihydroxide, di-n-nonylzirconium dihydroxide, di-n-isononylzirconium dihydroxide, di-n-decylzirconium dihydroxide, di-n-isodecylzirconium dihydroxide, dimethyltitanium dihydroxide, diethyltitanium dihydroxide, di-n-propyltitanium dihydroxide, diisopropyltitanium dihydroxide, di-n-butyltitanium dihydroxide Sid, diisobutyltitanium dihydroxide, di-n-pentyltitanium dihydroxide, diisopentyltitanium dihydroxide, di-n-hexyltitanium dihydroxide, diisohexyltitanium dihydroxide, di-n-heptyltitanium dihydroxide, diisoheptyltitanium dihydroxide, di-n-octyltitanium dihydroxide, di-n-isooctyltitanium dihydroxide, di-n-nonyltitanium dihydroxide, di-n-isononyltitanium dihydroxide, di-n-decyltitanium dihydroxide, di-n-isodecyltitanium dihydroxide,Dimethyl hafnium dihydroxide, diethyl hafnium dihydroxide, di-n-propyl hafnium dihydroxide, diisopropyl hafnium dihydroxide, di-n-butyl hafnium dihydroxide, diisobutyl hafnium dihydroxide, di-n-pentyl hafnium dihydroxide, diisopentyl hafnium dihydroxide, di-n-hexyl hafnium dihydroxide, diisohexyl hafnium dihydroxide, di-n-heptyl hafnium dihydroxide, diisoheptyl hafnium dihydroxide, di-n-octyl hafnium dihydroxide, di-n-isooctylhafnium dihydroxide, di-n-nonylhafnium dihydroxide, di-n-isononylhafnium dihydroxide, di-n-decylhafnium dihydroxide, di-n-isodecylhafnium dihydroxide, monomethylzirconium trihydroxide, monoethylzirconium trihydroxide, mono-n-propylzirconium trihydroxide, monoisopropylzirconium trihydroxide, mono-n-butylzirconium trihydroxide, monoisobutylzirconium trihydroxide, mono- n-Pentylzirconium trihydroxide, monoisopentylzirconium trihydroxide, mono-n-hexylzirconium trihydroxide, monoisohexylzirconium trihydroxide, mono-n-heptylzirconium trihydroxide, monoisoheptylzirconium trihydroxide, mono-n-octylzirconium trihydroxide, mono-n-isooctylzirconium trihydroxide, mono-n-nonylzirconium trihydroxide, mono-n-isononylzirconium trihydroxide, mono-n-decylzirconium trihydroxide, mono-n-isodecylzirconium trihydroxide, monomethyltitanium trihydroxide, monoethyltitanium trihydroxide, mono-n-propyltitanium trihydroxide, monoisopropyltitanium trihydroxide, mono-n-butyltitanium trihydroxide, monoisobutyltitanium trihydroxide, mono-n-pentyltitanium trihydroxide, monoisopentyltitanium trihydroxide, mono-n-hexyltitanium trihydroxide, monoisohexyltitanium trihydroxide, mono-n-heptyltitanium trihydroxide,Monoisoheptyl titanium trihydroxide, mono-n-octyl titanium trihydroxide, mono-n-isooctyl titanium trihydroxide, mono-n-nonyl titanium trihydroxide, mono-n-isononyl titanium trihydroxide, mono-n-decyl titanium trihydroxide, mono-n-isodecyl titanium trihydroxide, monomethyl hafnium trihydroxide, monoethyl hafnium trihydroxide, mono-n-propyl hafnium trihydroxide, monoisopropyl hafnium trihydroxide, mono-n-butyl hafnium trihydroxide, monoisobutyl hafnium trihydroxide, mono-n-pentyl hafnium trihydroxide, monoisopropyl ... sopentylhafnium trihydroxide, mono-n-hexylhafnium trihydroxide, monoisohexylhafnium trihydroxide, mono-n-heptylhafnium trihydroxide, monoisoheptylhafnium trihydroxide, mono-n-octylhafnium trihydroxide, mono-n-isooctylhafnium trihydroxide, mono-n-nonylhafnium trihydroxide, mono-n-isononylhafnium trihydroxide, mono-n-decylhafnium trihydroxide, mono-n-isodecylhafnium trihydroxide, zirconium tetrahydroxide, titanium tetrahydroxide, and hafnium tetrahydroxide.

[0193] In some embodiments, the organometallic hydrolyzed compound is present in the AIGS film composition at least 0.005 wt% (50 ppm). In some embodiments, the organometallic hydrolyzed compound is present in the AIGS film composition in an amount of about 0.03 to about 3 wt%. In some embodiments, the organometallic hydrolyzed compound is present in the AIGS film composition in an amount of about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1.0, about 1.1, about 1.2, about 1.3, about 1.4, about 1.5, about 1.6, about 1.7, about 1.8, about 1.9, about 2.0, about 2.1, about 2.2, about 2.3, about 2.4, about 2.5, about 2.6, about 2.7, about 2.8, about 2.9, or about 3 wt%.

[0194] Method for producing hydrolyzed compound The method for preparing the hydrolyzed compound can be carried out by contacting the compound with moisture, an acidic solution or a basic solution. In one embodiment, 10 μl of 1N aqueous NaOH solution is added to 1 g of zirconium propoxide in 4 ml of ethanol. The reaction mixture is stirred at room temperature for 30 minutes, and then 10 μl of 1N aqueous hydrochloric acid solution is added to neutralize the reaction mixture. The resulting viscous liquid is used as the hydrolyzed product after removing volatiles in vacuum.

[0195] Spin coating In some embodiments, the nanostructure composition is deposited on the substrate using spin coating. In spin coating, typically a small amount of material is deposited at the center of a substrate loaded into a machine called a spinner, which is held in place by a vacuum. High speed rotation of the substrate through the spinner creates a centripetal force that spreads the material from the center to the edge of the substrate. Most of the material is spun away, but a certain amount remains on the substrate and as the rotation continues a thin film of material is formed on the surface. The final thickness of the film is determined by the nature of the deposited material and the substrate, in addition to the parameters selected for the spin process, such as spin speed, acceleration and spin time. Typical films use spin speeds of 1500-6000 rpm with spin times of 10-60 seconds. In some embodiments, the film is deposited at a very low speed, for example less than 1000 rpm. In some embodiments, the film is cast at about 300, about 400, about 500, about 600, about 700, about 800 or about 900 rpm.

[0196] Mist accumulation In some embodiments, the nanostructure composition is deposited on the substrate using mist deposition. Mist deposition is performed at room temperature and atmospheric pressure, and film thickness can be precisely controlled by varying the process conditions. During mist deposition, the liquid source material is transformed into a very fine mist and carried by nitrogen gas into the deposition chamber. The mist is then attracted to the wafer surface by a high voltage potential between the field screen and the wafer holder. Once the droplets have coalesced on the wafer surface, the wafer is removed from the chamber and thermally cured to evaporate the solvent. The liquid precursor is a mixture of the solvent and the material to be deposited. It is carried to the atomizer by pressurized nitrogen gas. Price, SC, et al., “Formation of Ultra-Thin Quantum Dot Films by Mist Deposition”, ESC Transactions 11:89-94 (2007).

[0197] Spray Coating In some embodiments, the nanostructure composition is deposited on the substrate using spray coating. A typical apparatus for spray coating is composed of a spray nozzle, a sprayer, a precursor solution, and a carrier gas. In the spray deposition process, the precursor solution is broken into micro-sized droplets by a carrier gas or atomization (e.g., ultrasonic, air blast, or electrostatic). The droplets coming out of the sprayer are accelerated on the substrate surface through a nozzle with the help of a carrier gas that is controlled and adjusted as required. The relative motion between the spray nozzle and the substrate is defined by design for the purpose of complete coverage on the substrate.

[0198] In some embodiments, the application of the nanostructure composition further comprises a solvent. In some embodiments, the solvent for the application of the nanostructure composition is water, an organic solvent, an inorganic solvent, a halogenated organic solvent, or a mixture thereof. Exemplary solvents include, but are not limited to, water, DO, acetone, ethanol, dioxane, ethyl acetate, methyl ethyl ketone, isopropanol, anisole, γ-butyrolactone, dimethylformamide, N-methylpyrrolidinone, dimethylacetamide, hexamethylphosphoramide, toluene, dimethylsulfoxide, cyclopentanone, tetramethylene sulfoxide, xylene, ε-caprolactone, tetrahydrofuran, tetrachloroethylene, chloroform, chlorobenzene, dichloromethane, 1,2-dichloroethane, 1,1,2,2-tetrachloroethane, or a mixture thereof.

[0199] Inkjet printing Solvents suitable for inkjet printing of nanostructures are known to those of skill in the art. In some embodiments, the organic solvent is a substituted aromatic or heteroaromatic solvent as described in U.S. Patent Application Publication No. 2018 / 0230321, which is incorporated by reference in its entirety.

[0200] In some embodiments, the organic solvent used in the nanostructure composition used as the inkjet printing formulation is defined by its boiling point, viscosity, and surface tension. The properties of organic solvents suitable for inkjet printing formulations are shown in Table 1.

[0201] [Table 1]

[0202] In some embodiments, the organic solvent has a boiling point at 1 atmosphere of about 150° C. to about 350° C., about 150° C. to about 300° C., about 150° C. to about 250° C., about 150° C. to about 200° C., about 200° C. to about 350° C., about 200° C. to about 300° C., about 200° C. to about 250° C., about 250° C. to about 350° C., about 250° C. to about 300° C., or about 300° C. to about 350° C. at 1 atmosphere.

[0203] In some embodiments, the organic solvent has a viscosity of about 1 mPa·s to about 15 mPa·s. In some embodiments, the organic solvent has a viscosity of about 1 mPa·s to about 15 mPa·s, about 1 mPa·s to about 10 mPa·s, about 1 mPa·s to about 8 mPa·s, about 1 mPa·s to about 6 mPa·s, about 1 mPa·s to about 4 mPa·s, about 1 mPa·s to about 2 mPa·s, about 2 mPa·s to about 15 mPa·s, about 2 mPa·s to about 10 mPa·s, about 2 mPa·s to about 8 mPa·s, about 2 mPa·s to about 6 ... The viscosity of the composition is from about 4 mPa·s to about 4 mPa·s, from about 4 mPa·s to about 15 mPa·s, from about 4 mPa·s to about 10 mPa·s, from about 4 mPa·s to about 8 mPa·s, from about 4 mPa·s to about 6 mPa·s, from about 6 mPa·s to about 15 mPa·s, from about 6 mPa·s to about 10 mPa·s, from about 6 mPa·s to about 8 mPa·s, from about 8 mPa·s to about 15 mPa·s, from about 8 mPa·s to about 10 mPa·s, or from about 10 mPa·s to about 15 mPa·s.

[0204] In some embodiments, the organic solvent has a surface tension of about 20 dynes / cm to about 50 dynes / cm. In some embodiments, the organic solvent has a surface tension of about 20 dynes / cm to about 50 dynes / cm, about 20 dynes / cm to about 40 dynes / cm, about 20 dynes / cm to about 35 dynes / cm, about 20 dynes / cm to about 30 dynes / cm, about 20 dynes / cm to about 25 dynes / cm, about 25 dynes / cm to about 50 dynes / cm, about 25 dynes / cm to about 40 ... The surface tension of the composition is from about 25 dyne / cm to about 35 dyne / cm, from about 25 dyne / cm to about 30 dyne / cm, from about 30 dyne / cm to about 50 dyne / cm, from about 30 dyne / cm to about 40 dyne / cm, from about 30 dyne / cm to about 35 dyne / cm, from about 35 dyne / cm to about 50 dyne / cm, from about 35 dyne / cm to about 40 dyne / cm, or from about 40 dyne / cm to about 50 dyne / cm.

[0205] In some embodiments, the organic solvent used in the nanostructure composition is an alkyl naphthalene, an alkoxy naphthalene, an alkyl benzene, an aryl, an alkyl substituted benzene, a cycloalkyl benzene, a C-C 20 It may be an alkane, a diaryl ether, an alkyl benzoate, an aryl benzoate, or an alkoxy substituted benzene.

[0206] In some embodiments, the organic solvent used in the nanostructure composition is 1-tetralone, 3-phenoxytoluene, acetophenone, 1-methoxynaphthalene, n-octylbenzene, n-nonylbenzene, 4-methylanisole, n-decylbenzene, p-diisopropylbenzene, pentylbenzene, tetralin, cyclohexylbenzene, chloronaphthalene, 1,4-dimethylnaphthalene, 3-isopropylbiphenyl, p-methylcumene, dipentylbenzene, o-diethylbenzene, m-diethylbenzene, p-diethylbenzene, 1,2,3,4-tetramethylbenzene, 1,2,3,5-tetramethylbenzene, 1,2,4,5-tetramethylbenzene, butylbenzene, dodecylbenzene, 1-methylnaphthalene, 1,2,4-trichlorobenzene, diphenyl ether, diphenylmethane, 4-isopropylbiphenyl, benzyl benzoate, 1,2-bi(3,4-dimethylphenyl)ethane, 2-isopropylnaphthalene, dibenzyl ether, or a combination thereof. In some embodiments, the organic solvent used in the nanostructure composition is 1-methylnaphthalene, n-octylbenzene, 1-methoxynaphthalene, 3-phenoxytoluene, cyclohexylbenzene, 4-methylanisole, n-decylbenzene, or a combination thereof.

[0207] In some embodiments, the organic solvent is an anhydrous organic solvent, hi some embodiments, the organic solvent is a substantially anhydrous organic solvent.

[0208] In some embodiments, the organic solvent is a non-volatile monomer or combination of monomers selected from the list presented above.

[0209] In some embodiments, the weight percent of the organic solvent in the nanostructure composition is about 70% to about 99%. In some embodiments, the weight percent of the organic solvent in the nanostructure composition is about 70% to about 99%, about 70% to about 98%, about 70% to about 95%, about 70% to about 90%, about 70% to about 85%, about 70% to about 80%, about 70% to about 75%, about 75% to about 99%, about 75% to about 98%, about 75% to about 95%, about 75% to about 90%, about 75% to about 85%, about 75% to about 80%, about 80% to about 99%, about 80% to about 98%, about 80% to about 95%, about 80% to about 90%, about 80% to about 85%, about 85% to about 99%, about 85% to about 98%, about 85% to about 95%, about 85% to about 90%, about 90% to about 99%, about 90% to about 98%, about 90% to about 95%, about 95% to about 99%, about 95% to about 98%, or about 98% to about 99%. In some embodiments, the weight percent of organic solvent in the nanostructure composition is about 95% to about 99%.

[0210] Film hardening In some embodiments, the composition is thermally cured to form the nanostructured layer. In some embodiments, the composition is cured using UV light. In some embodiments, the nanostructured composition is coated directly onto the barrier layer of the nanostructured film, and then an additional barrier layer is deposited onto the nanostructured layer to form the nanostructured film. A support substrate can be employed beneath the barrier film to enhance strength, stability, and coating uniformity, and to prevent material non-uniformity, bubble formation, wrinkling or folding of the barrier layer material or other materials. Additionally, one or more barrier layers can be deposited above the nanostructured layer to seal the material between the upper and lower barrier layers. Optionally, the barrier layers can be deposited as a laminate film, optionally sealed or further processed, before the nanostructured film is incorporated into a particular lighting device. The nanostructured composition deposition process can include additional or different components, as will be appreciated by those skilled in the art. Such embodiments allow for in-line process tuning of nanostructured emission characteristics such as brightness and color (e.g., to adjust the quantum film white point), as well as nanostructure film thickness and other properties. Additionally, these embodiments allow for periodic testing of the nanostructured film properties during production, and any desired toggling to achieve precise nanostructured film properties. Such testing and adjustments can also be accomplished without modifying the mechanical configuration of the processing line, since computer programs can be employed to electronically vary the amounts of each of the mixtures used in forming the nanostructured film.

[0211] It has been discovered that nanostructured films with high PCEs are obtained if the AIGS nanocrystals are not exposed to blue or UV light prior to processing the film to provide an oxygen-free environment for the nanostructures. (a) encapsulating the film with an oxygen barrier prior to thermal treatment and / or exposure to blue light for PCE measurement; (b) the use of oxygen-reactive materials as part of the formulation during heat treatment or light exposure; and / or (c) Temporary blocking of oxygen through the use of a sacrificial barrier layer.

[0212] In some embodiments, the improvement of PCE can be achieved by any method capable of forming an oxygen barrier on the AIGS layer. In mass production of devices containing these AIGS-CC layers, encapsulation can be performed using a deposition process. A typical process flow in this case includes inkjet printing of an AIGS layer, followed by curing with UV exposure, baking at 180° C. to remove volatiles, deposition of an organic planarization layer, and then deposition of an inorganic barrier layer. Techniques used to deposit the inorganic layer include atomic layer deposition (ALD), molecular layer deposition (MLD), chemical vapor deposition (CVD) (with or without plasma enhancement), pulsed vapor deposition (PVD), sputtering, metal evaporation, and the like. Other potential encapsulation methods include solution-processed or printed organic layers, UV or thermal curable adhesives, lamination with barrier films, and the like.

[0213] In some embodiments, the membrane is encapsulated in an inert atmosphere, hi some embodiments, the membrane is encapsulated in a nitrogen or argon atmosphere.

[0214] Oxygen-reactive materials include any material that is more reactive to oxygen than the AIGS nanostructures. Examples of oxygen-reactive materials include, but are not limited to, phosphines, phosphites, organometallic precursors, titanium nitride, and tantalum nitride. In some embodiments, phosphines are C 1~20 The phosphine may be any one of trialkylphosphines. In one embodiment, the phosphine is trioctylphosphine. In some embodiments, the phosphite may be trialkylphosphite, alkylarylphosphite, or triarylphosphite. In some embodiments, the organometallic precursor may be trialkylaluminum, trialkylgallium, trialkylindium, dialkylzinc, etc.

[0215] Examples of sacrificial barrier layers include polymer layers that can be dissolved in a solvent and washed away. Examples of such polymers include, but are not limited to, polyvinyl alcohol, polyvinyl acetate, and polyethylene glycol. Other examples of sacrificial barrier layers include inorganic compounds or salts, such as lithium silicate and lithium fluoride. Examples of solvents that can be used to wash away the sacrificial layer include water and C 2 O 4 , such as alcohols (e.g., ethanol, methanol), halocarbons (e.g., methylene chloride and ethylene chloride), aromatic hydrocarbons (e.g., toluene, xylene), aliphatic hydrocarbons (e.g., hexane, octane, octadecene), tetrahydrofuran, and diethyl ether. 4~20 C such as ethyl acetate and ethyl acetate 2~20 Examples of the organic solvent include esters and the like.

[0216] Nanostructured Film Features and Embodiments In some embodiments, the nanostructured film of the present invention is used to form a display device. As used herein, a display device refers to any system that has an illuminated display. Such devices include, but are not limited to, liquid crystal displays (LCDs), televisions, computers, mobile phones, smartphones, personal digital assistants (PDAs), gaming devices, electronic reading devices, digital cameras, augmented reality / virtual reality (AR / VR) glasses, light projection systems, head-up displays, etc.

[0217] In some embodiments, the nanostructured film is part of a nanostructured color conversion layer.

[0218] In some embodiments, the display device includes a nanostructured color converter. In some embodiments, the display device includes a backplane, a display panel disposed on the backplane, and a nanostructured layer. In some embodiments, the nanostructured layer is disposed on the display panel. In some embodiments, the nanostructured layer includes a patterned nanostructured layer.

[0219] In some embodiments, the backplane includes a blue LED, an LCD, an OLED, or a micro LED.

[0220] In some embodiments, the nanostructured layer is disposed on the light source element. In some embodiments, the nanostructured layer comprises a patterned nanostructured layer. The patterned nanostructured layer may be prepared by any method known in the art. In one embodiment, the patterned nanostructured layer is prepared by inkjet printing of a solution of nanostructures. Suitable solvents for the solution include, but are not limited to, dipropylene glycol monomethyl ether acetate (DPMA), polyglycidyl methacrylate (PGMA), diethylene glycol monoethyl ether acetate (EDGAC), and propylene glycol methyl ether acetate (PGMEA). Volatile solvents may also be used for inkjet printing, as they allow for rapid drying. Volatile solvents include ethanol, methanol, 1-propanol, 2-propanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, ethyl acetate, and tetrahydrofuran. Alternatively, a "solvent-free" ink, in which the AIGS nanostructures are dispersed in the ink monomer, may be used for inkjet printing.

[0221] In some embodiments, the nanostructured layer has a thickness of about 1 μm to about 25 μm. In some embodiments, the nanostructured layer has a thickness of about 5 μm to about 25 μm. In some embodiments, the nanostructured layer has a thickness of about 10 μm to about 12 μm.

[0222] In some embodiments, the nanostructured display device exhibits a PCE of at least 32%. In some embodiments, the nanostructured molded article exhibits a PCE of 32-40%. In some embodiments, the nanostructured molded article exhibits a PCE of 33-40%, 34-40%, 35-40%, 36-40%, 37-40%, 38-40%, 39-40%, 33-39%, 34-39%, 35-39%, 36-39%, 37-39%, 38-39%, 33-38%, 34-38%, 35-38%, 36-38%, 37-38%, 33-37%, 34-37%, 35-37%, 36-37%, 33-36%, 34-36%, 35-36%, 33-35%, or 34-35%.

[0223] In some embodiments, the optical film including the nanostructured layer is substantially cadmium-free. As used herein, the term "substantially cadmium-free" is intended to mean that the nanostructure composition contains less than 100 ppm by weight of cadmium. The RoHS compliance definition requires that there should not be more than 0.01% by weight (100 ppm) of cadmium in the raw homogenous precursor material. Cadmium concentrations can be measured at parts per billion (ppb) levels by inductively coupled plasma mass spectrometry (ICP-MS) analysis. In some embodiments, the "substantially cadmium-free" optical film contains 10-90 ppm of cadmium. In other embodiments, the substantially cadmium-free optical film contains less than about 50 ppm, less than about 20 ppm, less than about 10 ppm, or less than about 1 ppm of cadmium.

[0224] Nanostructured Molded Articles In some embodiments, the present disclosure provides: (a) a first barrier layer; (b) a second barrier layer, and (c) a nanostructured layer between the first barrier layer and the second barrier layer; wherein the nanostructured layer comprises a population of AIGS nanostructures and nanostructures comprising one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or combinations thereof, and at least one organic resin.

[0225] In some embodiments, the nanostructures have a PWL of 480-545 nm.

[0226] In some embodiments, at least 80% of the emission is band-edge emission. In other embodiments, at least 90% of the emission is band-edge emission. In other embodiments, at least 95% of the emission is band-edge emission. In some embodiments, 92-98% of the emission is band-edge emission. In some embodiments, 93-96% of the emission is band-edge emission. In some embodiments, the nanostructured molded article exhibits a PCE of at least 32%. In some embodiments, the nanostructured molded article exhibits a PCE of 32-40%. In some embodiments, the nanostructured molded articles exhibit a PCE of 33-40%, 34-40%, 35-40%, 36-40%, 37-40%, 38-40%, 39-40%, 33-39%, 34-39%, 35-39%, 36-39%, 37-39%, 38-39%, 33-38%, 34-38%, 35-38%, 36-38%, 37-38%, 33-37%, 34-37%, 35-37%, 36-37%, 33-36%, 34-36%, 35-36%, 33-35%, or 34-35%.

[0227] Barrier Layer In some embodiments, the nanostructured molded article includes one or more barrier layers disposed on either one or both sides of the nanostructured layer. Suitable barrier layers protect the nanostructured layer and the nanostructured molded article from environmental conditions such as high temperature, oxygen, and moisture. Suitable barrier materials include non-yellowing transparent optical materials that are hydrophobic, chemically and mechanically compatible with the nanostructured molded article, exhibit light and chemical stability, and can withstand high temperatures. In some embodiments, the one or more barrier layers are index-matched to the nanostructured molded article. In some embodiments, the matrix material of the nanostructured molded article and the one or more adjacent barrier layers are index-matched to have similar refractive indices such that a large proportion of light transmitted through the barrier layer toward the nanostructured molded article is transmitted from the barrier layer to the nanostructured layer. This index matching reduces light loss at the interface between the barrier layer and the matrix material.

[0228] The barrier layer is suitably a solid material and can be a hardened liquid, gel, or polymer. The barrier layer can include flexible or non-flexible materials depending on the particular application. The barrier layer is generally a planar layer and can include any suitable shape and surface area configuration depending on the particular lighting application. In some embodiments, the one or more barrier layers are compatible with a lamination film processing technique, whereby a nanostructured layer is disposed on at least a first barrier layer and at least a second barrier layer is disposed on the nanostructured layer on the opposite side to the nanostructured layer to form a nanostructured molded article according to an embodiment of the present invention. Suitable barrier materials include any suitable barrier material known in the art. For example, suitable barrier materials include glass, polymers, and oxides. Suitable barrier layer materials include, but are not limited to, polymers such as polyethylene terephthalate (PET); oxides such as silicon oxide, titanium oxide, or aluminum oxide (e.g., SiO2, SiO3, TiO2, or Al2O3); and suitable combinations thereof. In some embodiments, each barrier layer of the nanostructured molded article comprises at least two layers comprising different materials or compositions, where the multi-layer barrier eliminates or reduces alignment of pinhole defects in the barrier layers and provides an effective barrier against oxygen and moisture penetration into the nanostructured layer. The nanostructured layer may comprise any suitable material or combination of materials, and any suitable number of barrier layers on either or both sides of the nanostructured layer. The material, thickness, and number of barrier layers will depend on the particular application, and are suitably selected to maximize the barrier protection and brightness of the nanostructured layer while minimizing the thickness of the nanostructured molded article. In some embodiments, each barrier layer comprises a laminate film, in some embodiments a bi-laminate film, where the thickness of each barrier layer is thick enough to eliminate wrinkles during roll-to-roll or laminate manufacturing processes. The number or thickness of the barriers may further depend on legal toxicity guidelines in embodiments where the nanostructures contain heavy metals or other toxic materials, which may require more or thicker barrier layers. Additional considerations regarding the barriers include cost, availability, and mechanical strength.

[0229] In some embodiments, the nanostructured film includes two or more barrier layers adjacent to each side of the nanostructured layer, e.g., two or three layers on each side, or two barrier layers on each side of the nanostructured layer, hi some embodiments, each barrier layer includes a thin glass sheet, e.g., a glass sheet having a thickness of about 100 μm, 100 μm or less, or 50 μm or less.

[0230] Each barrier layer of the nanostructured film of the present invention can have any suitable thickness, which will depend on the specific requirements and characteristics of the lighting device and application, as well as the individual film components, such as the barrier layer and the nanostructured layer, as would be understood by one of ordinary skill in the art. In some embodiments, each barrier layer can have a thickness of 50 μm or less, 40 μm or less, 30 μm or less, 25 μm or less, 20 μm or less, or 15 μm or less. In certain embodiments, the barrier layer includes an oxide coating, which can include materials such as silicon oxide, titanium oxide, aluminum oxide (e.g., SiO2, SiO3, TiO2, or Al2O3). The oxide coating can have a thickness of about 10 μm or less, 5 μm or less, 1 μm or less, or 100 nm or less. In certain embodiments, the barrier includes a thin oxide coating with a thickness of about 100 nm or less, 10 nm or less, 5 nm or less, or 3 nm or less. The top and / or bottom barrier can consist of an oxide thin film coating, or can include an oxide thin film coating and one or more additional material layers.

[0231] Display device having nanostructured color conversion layer In some embodiments, the present invention provides (a) a first light-emitting display panel; (b) a backlight unit configured to provide a first light to the display panel; and (c) a color filter including at least one pixel region including a color conversion layer; The present invention provides a display device comprising:

[0232] In some embodiments, the color filter is composed of at least 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 pixel regions. In some embodiments, when blue light is incident on the color filter, red light, white light, green light, and / or blue light can be emitted through the pixel regions, respectively. In some embodiments, the color filter is as described in U.S. Pat. No. 9,971,076, which is incorporated by reference in its entirety.

[0233] In some embodiments, each pixel region includes a color conversion layer. In some embodiments, the color conversion layer includes nanostructures described herein configured to convert incident light to a first color of light. In some embodiments, the color conversion layer includes nanostructures described herein configured to convert incident light to blue light.

[0234] In some embodiments, the display device includes 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 color conversion layers. In some embodiments, the display device includes one color conversion layer comprising the nanostructures described herein. In some embodiments, the display device includes two color conversion layers comprising the nanostructures described herein. In some embodiments, the display device includes three color conversion layers comprising the nanostructures described herein. In some embodiments, the display device includes four color conversion layers comprising the nanostructures described herein. In some embodiments, the display device includes at least one red color conversion layer, at least one green color conversion layer, and at least one blue color conversion layer.

[0235] In some embodiments, the color conversion layer has a thickness of about 3 μm to about 10 μm, about 3 μm to about 8 μm, about 3 μm to about 6 μm, about 6 μm to about 10 μm, about 6 μm to about 8 μm, or about 8 μm to about 10 μm. In some embodiments, the color conversion layer has a thickness of about 3 μm to about 10 μm.

[0236] The nanostructured color conversion layer can be deposited by any suitable method known in the art, including, but not limited to, painting, spray coating, solvent spraying, wet coating, adhesive coating, spin coating, tape coating, roll coating, flow coating, inkjet printing, photoresist patterning, drop casting, blade coating, mist deposition, or combinations thereof. In some embodiments, the nanostructured color conversion layer is deposited by photoresist patterning. In some embodiments, the nanostructured color conversion layer is deposited by inkjet printing.

[0237] Compositions Comprising AIGS Nanostructures and Ligands In some embodiments, the AIGS nanostructure composition further comprises one or more ligands, including amino ligands, polyamino ligands, mercapto ligands, phosphino ligands, silane ligands, and polymeric or oligomeric chains such as polyethylene glycol having amine and silane groups.

[0238] In some embodiments, the amino ligand has formula I: [ka] During the ceremony, x is 1 to 100; y is 0 to 100, and R 2 is C1~ 20 It is an alkyl.

[0239] In some embodiments, the polyamino ligand is a polyaminoalkane, a polyaminecycloalkane, a polyaminoheterocycle, a polyamino-functionalized silicone, or a polyamino-substituted ethylene glycol. In some embodiments, the polyamino ligand is a C2- 20 Alkane or C2~ 20In some embodiments, the polyamino-ligand is a cycloalkane, optionally containing one or two amino groups in place of carbon groups. In some embodiments, the polyamino-ligand is selected from the group consisting of ethylenediamine, 1,2-diaminopropane, 1,2-diamino-2-methylpropane, N-methyl-ethylenediamine, N-ethyl-ethylenediamine, N-isopropyl-ethylenediamine, N-cyclohexyl-ethylenediamine, N-cyclohexyl-ethylenediamine, N-octyl-ethylenediamine, N-decyl-ethylenediamine, N-dodecyl-ethylenediamine, N,N-dimethyl-ethylenediamine, N,N-diethyl-ethylenediamine, N,N'- Diethyl-ethylenediamine, N,N'-diisopropylethylenediamine, N,N,N'-trimethyl-ethylenediamine, diethylenetriamine, N-isopropyl-diethylenetriamine, N-(2-aminoethyl)-1,3-propanediamine, triethylenetetramine, N,N'-bis(3-aminopropyl)ethylenediamine, N,N'-bis(2-aminoethyl)-1,3-propanediamine, tris(2-aminoethyl)amine, tetraethylenepentamine, pentaethylenehexamine, 2-(2-amino-ethyl)a (amino)ethanol, N,N-bis(hydroxyethyl)ethylenediamine, N-(hydroxyethyl)diethylenetriamine, N-(hydroxyethyl)triethylenetetramine, piperazine, 1-(2-aminoethyl)piperazine, 4-(2-aminoethyl)morpholine, polyethyleneimine, 1,3-diaminopropane, 1,4-diaminobutane, 1,3-diaminopentane, 1,5-diaminopentane, 2,2-dimethyl-1,3-propanediamine, hexamethylenediamine, 2-methyl-1,5-diaminopropane, 1,7-diamino Aminoheptane, 1,8-diaminooctane, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 1,9-diaminononane, 1,10-diaminodecane, 1,12-diaminododecane, N-methyl-1,3-propanediamine, N-ethyl-1,3-propanediamine, N-isopropyl-1,3-propanediamine, N,N-dimethyl-1,3-propanediamine, N,N'-dimethyl-1,3-propanediamine, N,N'-diethyl-1,3-propanediamine, N,N'-Diisopropyl-1,3-propanediamine, N,N,N'-Trimethyl-1,3-propanediamine, 2-Butyl-2-ethyl-1,5-pentanediamine, N,N'-Dimethyl-1,6-hexanediamine, 3,3'-Diamino-N-methyl-dipropylamine, N-(3-aminopropyl)-1,3-propanediamine, Spermidine, Bis(hexamethylene)triamine, N,N',N''-Trimethyl-bis(hexamethylene)triamine, 4-Amino-1,8-octanediamine, N,N'-Bis(3-aminopropyl)-1,3-propanediamine, Spermidine permine, 4,4'-methylenebis(cyclohexylamine), 1,2-diaminocyclohexane, 1,4-diaminocyclohexane, 1,3-cyclohexanebis(methylamine), 1,4-cyclohexanebis(methylamine), 1,2-bis(aminoethoxy)ethane, 4,9-dioxa-1,12-dodecanediamine, 4,7,10-trioxa-1,13-tridecanediamine, 1,3-diamino-hydroxy-propane, 4,4-methylenedipiperidine, 4-(aminomethyl)piperidine, 3-(4-aminobutyl)piperidine, or polyallylamine. In some embodiments, the polyamino-ligand is 1,3-cyclohexanebis(methylamine), 2,2-dimethyl-1,3-propanediamine, or tris(2-aminoethyl)amine.

[0240] In some embodiments, the polyamino ligand is a polyamino heterocyclic compound. In some embodiments, the polyamino heterocyclic compound is 2,4-diamino-6-phenyl-1,3,5-triazine, 6-methyl-1,3,5-triazine-2,4-diamine, 2,4-diamino-6-diethylamino-1,3,5-triazine, 2-N,4-N,6-N-tripropyl-1,3,5-triazine-2,4,6-triamine, 2,4-diaminopyrimidine, 2,4,6-triaminopyrimidine, 2,5-diaminopyridine, 2,4,5,6-tetraaminopyrimidine, pyridine-2,4,5-triamine, 1-(3-aminopropyl)imidazole, 4-phenyl-1H-imidazole-1,2- diamine, 1H-imidazole-2,5-diamine, 4-phenyl-N(1)-[(E)-phenylmethylidene]-1H-imidazole-1,2-diamine, 2-phenyl-1H-imidazole-4,5-diamine, 1H-imidazole-2,4,5-triamine, 1H-pyrrole-2,5-diamine, 1,2,4,5-tetrazine-3,6-diamine, N,N'-dicyclohexyl-1,2,4,5-tetrazine-3,6-diamine, N3-propyl-1H-1,2,4-triazole-3,5-diamine, or N,N'-bis(2-methoxybenzyl)-1H-1,2,4-triazole-3,5-diamine.

[0241] In some embodiments, the polyamino ligand is a polyamino-functionalized silicone. In some embodiments, the polyamino-functionalized silicone is [ka] It is one of the following.

[0242] In some embodiments, the polyamino ligand is a polyamino-substituted ethylene glycol. In some embodiments, the polyamino-substituted ethylene glycol is 2-[3-amino-4-[2-[2-amino-4-(2-hydroxyethyl)phenoxy]ethoxy]phenyl]ethanol, 1,5-diamino-3-oxapentane, 1,8-diamino-3,6-dioxaoctane, bis[5-chloro-1H-indole-2-YL-carbonyl-aminoethyl]-ethylene glycol, amino-PEG8-t-Boc-hydrazide, or 2-(2-(2-ethoxyethoxy)ethoxy)ethanamine.

[0243] In some embodiments, the mercapto ligand is (3-mercaptopropyl)triethoxysilane, 3,6-dioxa-1,8-octanedithiol; 6-mercapto-1-hexanol; mercaptosuccinic acid, mercaptoundecanoic acid, mercaptohexanoic acid, mercaptopropionic acid, mercaptoacetic acid, cysteine, methionine, and mercaptopoly(ethylene glycol).

[0244] In some embodiments, the silane ligand is an aminoalkyltrialkoxysilane or a thioalkyltrialkoxysilane. In some embodiments, the aminoalkyltrialkoxysilane is 3-aminopropyl)triethoxysilane or 3-mercaptopropyl)triethoxysilane.

[0245] In some embodiments, the ligands include, but are not limited to, aminopolyalkylene oxides (e.g., mw about 1000); (3-aminopropyl)trimethoxysilane; (3-mercaptopropyl)triethoxysilane; DL-α-lipoic acid; 3,6-dioxa-1,8-octanedithiol; 6-mercapto-1-hexanol; methoxypolyethylene glycol amines (mw about 500); poly(ethylene glycol) methyl ether thiol (mw about 800); diethylphenylphosphonite; dibenzyl N,N-diisopropyl phosphoramidite; di-tert-butyl N,N-diisopropyl phosphoramidite; tris(2-carboxyethyl)phosphine hydrochloride; poly(ethylene glycol) methyl ether thiol (mw about 2000); methoxypolyethylene glycol amines (mw about 750); acrylamide; and polyethyleneimine.

[0246] Specific combinations of ligands include aminopolyalkylene oxide (mw about 1000) and methoxypolyethylene glycol amine (mw about 500); amino-polyalkylene oxide (mw about 1000) and 6-mercapto-1-hexanol; aminopolyalkylene oxide (mw about 1000) and (3-mercaptopropyl)triethoxysilane; and 6-mercapto-1-hexanol and methoxypolyethylene glycol amine (mw about 500), which provided excellent dispersibility and thermal stability. See Example 9.

[0247] Films containing AIGS nanostructures and polyamino ligands exhibit higher film photoconversion efficiency (PCE), less wrinkling, and less film peeling compared to AIGS-containing films without polyamino ligands and compared to monoamino ligands. Thus, compositions containing AIGS-polyamino ligands are particularly suitable for use in nanostructured color conversion layers.

[0248] scattering medium The AIGS film may further include a scattering medium. Examples of scattering media that can be used include, but are not limited to, metal or metal oxide particles, air bubbles, and glass and polymer beads (solid or hollow). In some embodiments, the scattering medium has a spherical shape. In some embodiments, the scattering medium includes, but is not limited to, TiO2, SiO2, BaTiO3, BaSO4, and ZnO particles.

[0249] The following examples are illustrative, not limiting, of the products and processes described herein. Suitable variations and modifications of the variety of conditions, formulations, and other parameters normally encountered in the art and obvious to those skilled in the art in light of this disclosure are within the spirit and scope of the invention. EXAMPLES

[0250] Example 1: AIGS Core Synthesis The following typical AIGS core synthesis was used to prepare sample ID1: 4 mL of 0.06 M CH3CO2Ag in oleylamine, 1 mL of 0.2 M InCl3 in ethanol, 1 mL of 0.95 M sulfur in oleylamine, and 0.5 mL of dodecanethiol were injected into a flask containing 5 mL of degassed octadecene, 300 mg of trioctylphosphine oxide, and 170 mg of gallium acetylacetonate. The mixture was heated to 40 °C for 5 min, after which the temperature was increased to 210 °C and held for 100 min. After cooling to 180 °C, 5 mL of trioctylphosphine was added. The reaction mixture was transferred to a glove box and diluted with 5 mL of toluene. The final AIGS product was precipitated by adding 75 mL of ethanol, centrifuging, and redispersing in toluene. Samples ID2 and 3 were also prepared using this method. The optical properties of the AIGS cores were measured and summarized in Table 1. The size and morphology of the AIGS cores were evaluated by transmission electron microscopy (TEM).

[0251] [Table 2]

[0252] Example 2: AIGS nanostructures subjected to ion exchange treatment The following typical ion-exchange procedure was used to prepare sample ID4: 2 mL of a 0.3 M solution of gallium oleate in octadecene and 12 mL of oleylamine were introduced into a flask and degassed. The mixture was heated to 270 °C. 1 mL of a 0.95 M solution of sulfur in oleylamine and 1 mL of a premixed solution of isolated AIGS cores (15 mg / mL) were simultaneously injected. The reaction was stopped after 30 min. The final product was transferred to a glove box, washed with toluene / ethanol, centrifuged, and redispersed in toluene. Samples ID4-8 were also prepared using this method. The optical properties of the AIGS nanostructures thus produced are summarized in Table 2. Ion-exchange with gallium ions resulted in almost complete band-edge emission. An increase in the average grain size was observed by TEM.

[0253] [Table 3]

[0254] Example 3: Ion exchange treatment of gallium halide and trioctylphosphine A room-temperature ion-exchange reaction with the AIGS nanostructures was carried out by adding a GaI3 solution (0.01–0.25 M) in trioctylphosphine to the AIGS QDs and keeping them at room temperature for 20 h. This treatment significantly enhanced the band-edge emission in Table 3 while essentially maintaining the peak wavelength (PWL).

[0255] The compositional changes before and after GaI3 addition were monitored by inductively coupled plasma atomic emission spectroscopy (ICP-AES) and energy dispersive X-ray spectroscopy (EDS), as shown in Table 3. The composite images of In and Ga elemental distribution before and after GaI3 / TOP treatment showed a radial distribution from In to Ga, indicating that the ion-exchange treatment created a gradient of higher gallium content near the surface of the nanostructure and lower gallium content in the center.

[0256] [Table 4]

[0257] Example 4: AIGS ion exchange treatment using oxygen-free Ga source Samples ID14 and 15 were prepared using the following typical processing of AIGS nanoparticles using an oxygen-free Ga source: 400 mg of GaCl3 dissolved in 400 μL of toluene was added to 8 mL of degassed oleylamine, followed by 40 mg of AIGS cores, followed by 1.7 mL of 0.95 M sulfur in oleylamine. After heating to 240 °C, the reaction was held for 2 h and then cooled. The final product was transferred to a glove box, washed with toluene / ethanol, centrifuged, and redispersed in toluene. Samples ID15 and 16 were also prepared using this method. Samples ID11-13 were prepared using the method of Example 2. The optical properties of the processed AIGS materials are shown in Table 4.

[0258] [Table 5]

[0259] As shown in Table 4, when oleylamine is used as the solvent, the quantum yield of the processed AIGS nanostructures can be improved by using Ga(III) chloride rather than Ga(III) acetylacetonate or gallium oleate. The final material ion-exchanged with Ga(III) chloride exhibited similar size and similar band edge characteristics for trap emission as the starting nanostructures. Thus, the increase in quantum yield (QY) is not simply due to an increase in the trap emission component. It was also unexpectedly found that when Ga(III) iodide was used instead of Ga(III) chloride, the AIGS nanostructures dissolved in the reaction mixture and no ion exchange occurred.

[0260] High-resolution TEM with energy dispersive X-ray spectroscopy (EDS) of sample 14 indicates that the nanostructures likely contain a slight gradient of lower In from the center of the AIGS nanostructure towards the surface, which results from processing under these conditions in a process where In is exchanged out of the AIGS structure and replaced by Ga, but Ag is present in the entire structure rather than growing a distinct layer of GS. This may also contribute to the improved quantum yield of the nanostructures due to less strain.

[0261] Example 5: AIGS cores by hot injection of preformed Ag2S nanostructures mixed with preformed In-Ga reagents To prepare Ag2S nanostructures, 0.5 g of AgI and 2 mL of oleylamine were added to a 20 mL vial under N2 atmosphere and stirred at 58 °C until a clear solution was obtained. In another 20 mL vial, 5 mL of DDT and 9 mL of 0.95 M sulfur in oleylamine were mixed. The DDT+S-OYA mixture was added to the AgI solution and stirred at 58 °C for 10 min. The obtained Ag2S nanoparticles were used without washing.

[0262] To prepare the In-Ga reagent mixture, 1.2 g Ga(acetylacetonate)3, 0.35 g InCl3, 2.5 mL oleylamine, and 2.5 mL ODE were added to a 100 mL flask. The mixture was heated to 210 °C under N2 atmosphere and held for 10 min. An orange viscous product was obtained.

[0263] To form the AIGS nanoparticles, 1.75 g TOPO, 23 mL oleylamine, and 25 mL ODE were added to a 250 mL flask under N2. After degassing under vacuum, the solvent mixture was heated to 210 °C over 40 min. In a 40 mL vial, Ag2S and the above In-Ga reagent mixture were mixed at 58 °C and transferred to a syringe. The Ag-In-Ga mixture was then injected into the 210 °C solvent mixture and held for 3 h. After cooling to 180 °C, 5 mL trioctylphosphine was added. The reaction mixture was transferred to a glove box and diluted with 50 mL toluene. The final product was precipitated by adding 150 mL ethanol, centrifuging, and redispersing in toluene. The AIGS nanostructures were then ion-exchanged by the method described in Example 4. The optical properties of the material produced by this method are shown in Table 5, scaled up to 24 times as described above.

[0264] [Table 6]

[0265] Example 7 Repeated gallium ion exchange improves the photoluminescence stability of AIGS nanostructures 7.1 First Ion Exchange Process Oleylamine (OYA, 2.5 L) is degassed under vacuum at 40° C. for 40 minutes. AIGS nanostructures (25.4 g in toluene) are added, followed by GaCl3 (127 g in minimum toluene) and sulfur dissolved in OYA (0.95 M, 570 mL). The mixture is heated to 240° C. over 40 minutes and held for 4 hours. After cooling, the mixture is diluted with one volume of toluene. After removing by-products by centrifugation, the material is washed with two volumes of ethanol, recovered by centrifugation, and redissolved in toluene. After the second wash, the nanostructures are dissolved in heptane and stored.

[0266] 7.2 Second Ion Exchange Process Oleylamine (OYA, 960 mL) is degassed under vacuum at 40° C. for 20 min. AIGS ion-exchanged nanostructures as in Example 7.1 (12 g in heptane) are added to the OYA, followed by GaCl3 (22.5 g in a minimum amount of toluene), then sulfur dissolved in OYA (0.95 M, 100 mL). The mixture is heated to 240° C. over 40 min and held for 3 h. After cooling, the mixture is diluted with 1 volume of toluene, washed (precipitated with 1.6 volumes of ethanol and centrifuged), and redispersed in toluene or heptane as required. If ligand exchange of the ink formulation is to be performed, a further ethanol wash is performed and the QDs are redispersed in heptane.

[0267] 7.3 Alternative Second Ion Exchange Process Oleylamine (15 mL) is degassed under vacuum at 60° C. for 20 min. GaCl3 (360 mg in a minimum amount of toluene) is added to the OYA, followed by AIGS as in Example 7.1 (200 mg in heptane), then sulfur dissolved in OYA (0.95 M, 1.6 mL). The mixture is heated to 240° C. over 40 min and held for 3 h. After cooling, the mixture is washed as described in Example 7.1.

[0268] 7.4 Alternative Second Ion Exchange Process This example was carried out as described for Example 7.3, but on a three-fold scale.

[0269] 7.5 Alternative Second Ion Exchange Processes Oleylamine (10 mL) and oleic acid (5 mL) are degassed under vacuum at 90° C. for 20 min. (Ga(NMe3)3)2 (206 mg) and GaCl3 (180 mg in a minimum amount of toluene) are added, followed by AIGS (200 mg in heptane) as in Example 7.1. After heating to 130° C., TMS2S (0.65 mL of a 50% solution in ODE) is added over 20 min and the mixture is held for 2.5 h. After cooling, the mixture is washed as described in Example 7.1.

[0270] 7.6 Results AIGS nanostructures were subjected to an ion-exchange process to exchange In for Ga. The higher temperature used in this process compared to the core growth (240 °C vs. 210 °C) led to increased ripening and an average size larger than the untreated nanostructures. The nanostructures exhibit a poorly differentiated shell structure, which can be observed in cross-sectional TEM elemental mapping. The lack of a higher band gap shell is expected to limit the retention of photoluminescence in these materials during film processing.

[0271] After the second ion-exchange process, the average TEM size did not increase (Figures 2A-2C), but TEM elemental mapping showed that the QDs had a more distinct gradient towards Ga-rich (higher band gap) regions.

[0272] The elemental compositions of the single ion exchange process and the multiple ion exchange process are shown in Table 6. Values ​​are average values ​​of 10-20 samples from Examples 7.1 and 7.2.

[0273] [Table 7]

[0274] The properties of the ion-exchanged AIGS nanostructures are shown in Table 7. Metal ratios are molar ratios determined by ICP.

[0275] [Table 8]

[0276] The film PCE retained after UV curing and 180° C. baking is significantly improved by the second ion-exchange process, as shown in Table 8. This is believed to be due to the process of increasing the Ga concentration in the outer layer of the nanostructures, leading to a gradient into the higher bandgap region introduced by ion-exchange.

[0277] [Table 9]

[0278] Example 8 - Compositions containing AIGS nanostructures and polyamino ligands Abbreviation - Jeffamine - Jeffamine M-1000 - HDDA - 1-6 Hexanediol Diacrylate - Bismethylamine - 1,3 Cyclohexanebismethylamine - PCE - Photon Conversion Efficiency

[0279] The crude AIGS QD growth solution was purified by washing with ethanol and redispersing in heptane (solution 1). 6-mercapto-1-hexanol was added to solution 1 and heated at 50°C for 30 min, then washed with ethanol and redispersed in heptane (solution 2). 2 μL of 6-mercapto-1-hexanol was added per 100 mg of QD inorganic solid. Jeffamine and HDDA were added to solution 2 for the ligand exchange step, heated at 80°C for 1 h, precipitated with heptane, and redispersed in HDDA (solution 3). 83 mg of Jeffamine was added per 100 mg of QD inorganic solid. 0.42 g of HDDA was added per 100 mg of QD inorganic solid. Solution 3 and HDDA were added to an inkjet ink composition containing 10 wt% TiO2 and 90 wt% monomer. This inkjet formulation had a composition of 10 wt% QD inorganic mass, 4 wt% TiO2, and the remaining 86 wt% was a combination of ligands (bound and unbound), HDDA, monomers, photoinitiators, and other miscellaneous organics left over from the QD solution. This ink formulation was Solution 4.

[0280] To solution 4 was added the polyamino ligand bismethylamine (50 mg of bismethylamine per 100 mg of QD inorganic solid), and the composition was then cast as a film.

[0281] Film Cast Solution 4 was spin-coated onto a 2" x 2" glass substrate. The film was cured with a UV LED curing lamp. The film was then tested for photoconversion efficiency (PCE), a measure of brightness. The film was then baked for 30 minutes with a hot plate set at 180°C, just above the hot plate. Alternatively, the film was baked in direct contact with the hot surface on a hot plate set at 180°C for 10 minutes.

[0282] The film PCE was then tested. A 1" x 1" masked array of blue 448 nm LEDs provided the excitation light source for the film. An integrating sphere was placed over the film and connected to a fluorometer. See Figures 3A and 3B. The collected spectra were analyzed to determine the PCE.

[0283] PCE is the ratio of the number of green photons of forward emission to the number of blue photons generated by the test platform. The PCE, LRR and film morphology are reported in Table 9. Unexpectedly, the presence of the ligands 1,3-cyclohexanebis(methylamine), tris(2-aminoethyl)amine and 2,2-dimethyl-1,3-propanediamine resulted in high retention of PCE, high LRR and no wrinkles after baking at 180° C. compared to films without ligands.

[0284] [Table 10]

[0285] FIG. 1 shows the effect of diamine addition on film morphology. The films in FIG. 1 contained, from left to right: no addition (wrinkled); 2,2-dimethyl-1,3-propanediamine (diamine, non-wrinkled); cyclohexanemethylamine (monoamine, wrinkled); and tris(2-aminoethyl)amine (triamine, non-wrinkled). From left to right, the first and third films, which did not contain diamine, showed extensive wrinkling. In contrast, the second and fourth films showed no wrinkling. Unexpectedly, the use of diamino ligands in AIGS films led to a significant reduction in film wrinkling.

[0286] Example 9 - Testing of additional ligands on AIGS nanostructures In this study, additional ligands for AIGS nanoparticles were tested for improved QY, high compatibility, and good thermal stability. Furthermore, these ligands were evaluated for protecting the AIGS nanostructures from degradation and oxidation. Also, combinations of ligands that can be formulated into AIGS ink compositions were tested.

[0287] Ligand exchange with these ligands was carried out in organic solvents such as ethyl acetate, PGMEA, acetone, xylene, 1,2-dichlorobenzene (ODCB), butyl acetate, and diethylene glycol monoethyl ether (DGMEE).

[0288] AIGS nanostructures were ligand exchanged and co-passivated with ligands containing polymeric or oligomeric chains such as polyethylene glycol with amine and silane groups, and soft bases such as phosphino, mercapto, and combinations thereof.

[0289] Figure 4 shows the quantum yield values ​​of various individual ligands and AIGS nanostructures that have undergone a single ion exchange treatment as described herein. In this graph, NG: native AIGS; NG-NL1: aminopolyalkylene oxide approx. mw 1000; NG-NL2: (3-aminopropyl)trimethoxysilane; NG-NL3: (3-mercaptopropyl)triethoxysilane; NG-NL4: DL-α-lipoic acid; NG-NL5: 3,6-dioxa-1,8-octanedithiol; NG-NL6: 6-mercapto-1-hexanol; NG-NL7: methoxypolyethylene glycolamine 500; NG-NL8: poly(ethylene glycol) methyl ether thiol; (NG-NL10: dibenzyl N,N-diisopropyl phosphoramidite; NG-NL11: di-tert-butyl N,N-diisopropyl phosphoramidite; NG-NL12: tris(2-carboxyethyl)phosphine hydrochloride; NG-NL13: poly(ethylene glycol) methyl ether thiol Mn 2000; NG-NL14: methoxypolyethylene glycolamine 750; NG-NL15: acrylamide; and NG-NL16: polyethyleneimine).

[0290] As can be seen from Figure 4, treatment of AIGS nanostructures with 3-mercaptopropyl)triethoxysilane (NL3), 3,6-dioxa-1,8-octanedithiol (NL5), and 6-mercapto-1-hexanol (NL6) resulted in high QY (73.7%, 72.9%, and 76.1%, respectively). Thus, the present invention provides AIGS nanostructure compositions comprising at least one mercapto-substituted ligand that provides improved QY. It is believed that the mercapto-substituted ligand provides high QY by passivating the surface of the AIGS nanostructure and reducing defect emission. Amino-substituted ligands also improved QY.

[0291] In this single ligand study, the polyethylene glycol amine-substituted ligands (L1, L7, L8, and L13), the thiol-substituted ligands (L3, L5, and L6), and the silane ligand (L2) showed better QY compared to the native AIGS nanostructures. Also, ligands L1, L7, and L8 showed improved compatibility with the monomer when dispersed in HDDA.

[0292] FIG. 5 is a graph showing the QY% of various 2-ligand combinations that gave improved QY% (good combinations) and decreased QY% (bad combinations). Surface defects can be reduced by adding a thiol ligand. The combinations L6 and L7 gave better stability than the others. However, for relatively hydrophilic ink compositions, relatively hydrophilic ligands such as methoxypolyethylene glycol amine and poly(ethylene glycol) methyl ether thiol are better. The thiol also improves QY by passivating surface defects.

[0293] Suitable temperatures for the ligand exchange are from room temperature to 120° C. The total amount of ligands in the composition may be from 60% to 150% of the mass of the AIGS.

[0294] Table 10 shows the relative changes in QY, PWL and FWHM before and after ligand exchange with several ligands. Table 10 shows that L6&L7 was the most effective ligand combination for ink formulation, especially when combined with acrylate monomers. Combinations of L2&L7, L2&L6, and L2&L3, L6 and L7 gave excellent dispersibility and thermal stability. See Figure 6.

[0295] [Table 11]

[0296] Additionally, ligand combinations were investigated that showed good thermal stability when heated to 180° C. for 30 min in a glove box. Ligand combinations L6&L7, L2&L6, and L2&L3 provided better stability than single ligand L1. See FIG. 6.

[0297] The effect of different ratios of ligand combinations on QY was also studied. The weight ratio of the ligands was varied while keeping the total amount of ligands fixed. The best QY was achieved with a ratio of L6 to L7 of 7:3. See Figure 7. The combination of L6 and L7 showed improved QY over the native AIGS nanostructures, except for the 9:1 ratio. This mixture showed high QY but was difficult to purify due to lack of precipitation. Mixtures of L6&L2, L3&L7, and L5&L7 are good ligand mixtures for AIGS nanostructures. These ligand combinations can be used in combination with various monomers such as tetrahydrofurfuryl acrylate, tri(propylene glycol) diacrylate, 1,4-bis(acryloyloxy)butane, diethylene glycol ethyl ether arylate, isopronyl acrylate, hydroxypropyl acrylate, 2-(acryloyloxy)ethyl hydrogen succinate, and 1,6-hexanediol diacrylate.

[0298] Example 10 - Improvement of PCE in AIGS films In a N2-filled glovebox, AIGS QDs coated with appropriate ligands were mixed into inks containing one or more monomers, TiO2 scattering particles, and photoinitiators. These inks were spin-coated to cast films and cured with UV irradiation. The films were then baked on a hotplate at 180 °C for 30 min to remove residual volatile components. All of these processes were carried out in an inert atmosphere (in a N2-filled glovebox).

[0299] At this stage, the film can be measured in air by placing it face up over a blue LED light source. An integrating sphere connected to a spectrophotometer is placed on top of the QD film (see Figures 3A and 3B) and the emission spectrum of the film is captured. This measurement is also repeated on a blank glass substrate (no QDs). The blue light absorption and photon conversion efficiency (PCE) of the QD film are measured using the following equations: Blue light absorption = number of blue photons transmitted through the QD film / number of incident blue photons PCE = number of forward emitted green photons / number of incident blue photons

[0300] To investigate the effect of air and moisture during the measurements, the baked QD film was encapsulated before being removed from the N2-glove box. This was done by applying a few drops of a UV-curable transparent adhesive to the QD layer, then placing a glass coverslip and curing the adhesive by UV irradiation. The QD film thus encapsulated with glass and adhesive was measured in air using the method described above.

[0301] This result indicates that encapsulating the QD films prior to measurement in air is important to achieve high photon conversion efficiency (PCE). Table 11 shows the results from one set of films measured with and without encapsulation. For comparison, the PCE value of a typical QDCC film containing InP QDs is also shown. When measured encapsulated, the film containing AIGS nanostructures had higher post-bake PCE values ​​than InP at a much lower QD loading. With a blue light source (~6 mW / cm 2 Further improvement in PCE was achieved by illuminating the film by placing it on a 300 nm thick glass substrate (Figure 1A) for 1 h. Furthermore, the QDCC film made with AIGS QDs showed a much narrower emission (FWHM approx. 30 nm) compared to the film made with InP QDs (FWHM 36 nm). This is a result of the lower FWHM of the AIGS QDs in solution (34 nm vs. 39 nm) combined with the use of mono- and poly-amino ligands that allow for their good dispersion in the ink resin.

[0302] [Table 12]

[0303] Figure 9 shows the effect of encapsulation and blue light treatment on a wider range of samples. The PCE values ​​achieved with encapsulation were surprisingly significantly higher (32% higher) than without encapsulation.

[0304] The median FWHM of the film calcined at 180°C was 30.5 nm, which was further narrowed by encapsulation to 30.1 nm, possibly as a result of the film becoming brighter upon encapsulation.

[0305] Although the samples in this study were encapsulated using glass and adhesives, such improvements in PCE can be achieved with any method capable of forming an oxygen barrier to the QD layer. For mass production of devices containing these QDCC layers, encapsulation can be achieved using a deposition process. A typical process flow in this case would include inkjet printing of the QD layer, followed by curing with UV exposure, baking at 180 °C to remove volatiles, deposition of an organic planarization layer, and then deposition of an inorganic barrier layer. Techniques used to deposit the inorganic layer include atomic layer deposition (ALD), molecular layer deposition (MLD), chemical vapor deposition (CVD) (with or without plasma enhancement), pulsed vapor deposition (PVD), sputtering, metal evaporation, etc. Other potential encapsulation methods include solution-processed or printed organic layers, UV or thermally curable adhesives, lamination with barrier films, etc.

[0306] Example 11 Improved AIGS membrane using metal alkoxide Films that maintain their optical properties under 24-hour yellow light and air storage conditions are needed for applications in emerging advanced display technologies such as QD-OLED and QD microLED. Films containing zirconium isopropoxide were found to maintain at least 30% PCE under yellow light and air storage conditions, while films without zirconium propoxide showed a decrease in PCE from 35.8% to 14% (Table 12, item 1).

[0307] "Yellow light and air storage conditions" were established as follows: Films were made by spin-coating the AIGS ink onto glass substrates, then curing by irradiation with UV light (405 nm) and baking on a hotplate at 180°C for 30 minutes, all in a N2-filled glove box. The ink contained the following components:

[0308] [Table 13]

[0309] The films were then transferred to air and stored in a "yellow" room illuminated using white LED lighting covered with a blue-blocking filter. Typical illuminance values ​​and color coordinates for the yellow room are 140 lux, CIEx=0.52, CIEy=0.45, as measured by a Konica-Minolta CL-200A colorimeter. For reference, typical room lighting conditions without blue filtering are illuminance=620 lux, CIEx=0.38, CIEy=0.38.

[0310] To test the effect of air exposure on the PCE, films were taken at periodic intervals (3 hours, 1 day, 3 days), encapsulated using a second glass slide and a UV-curable transparent adhesive, and measured on the PCE platform. To further test the effect of long-term storage in air, the encapsulated films were baked again at 180°C for 30 minutes and measured on the PCE platform.

[0311] [Table 14]

[0312] The stability of the AIGS film was dramatically improved by adding zirconium(IV) propoxide or its hydrolysate in the AIGS ink, as shown in Table 13. As shown in Table 13, the PCE of the film could be maintained at 30.1-34.4% after 24 hours of yellow light storage, which is only slightly lower than the PCE of 35.8% of the air-free film.

[0313] Table 14 shows the results of films using inks containing different metal alkoxides. The addition of gallium or barium isopropoxide provides an improvement in the air stability of the films similar to that of zirconium propoxide.

[0314] [Table 15]

[0315] Without being bound to any particular theory, it is believed that the metal alkoxide forms a stabilizing shell around the AIGS nanostructures. In the classical sol-gel process, when tetraethyl orthosilicate (TEOS) is exposed to moisture in the air, a spontaneous hydrolysis and condensation reaction occurs. This results in the formation of a sol-gel three-dimensional network and, under extreme conditions, the formation of SiO2. Zr(OPr)4 is a typical sol-gel precursor. When the AIGS / Zr ink formulation is exposed to air, the sol-gel process does indeed occur. In-situ FTIR of AIGS / Zr(OPr)4 has revealed that the sol-gel peak at 3400 cm was observed by leaving the AIGS / Zr sample on the FTIR window for 5 minutes longer. -1 The intensity of the -OH stretching near ZrO increased significantly, whereas no such change was observed in the AIGS sample without Zr(OPr)4. This indicates that the in situ formed three-dimensional network acts as an oxygen barrier and prevents the formation of ZrO x (OH) y This is believed to be due to the formation of a high conduction band that confines excitons, especially electrons. The combination of these two processes effectively prevents the formation of reactive oxygen species (ROS) under light / air conditions, thus dramatically improving the light / air stability.

[0316] The inclusion of a phenolic additive that acts as an antioxidant and steric hindrance ligand can further improve film performance. Table 15 shows optical data from a series of films containing both zirconium propoxide and the phenolic additive pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0317] [Table 16]

[0318] Example 12 Use of bulky phenolic ancillary ligands Ligand exchange on the AIGS nanostructures was carried out with 6-mercaptohexanol and Jeffamine M1000 at 80 °C for 1 h. The AIGS nanostructures were then redispersed in monomer with ancillary ligands. The ink formulation contained 12% ligand-exchanged QDs, 10% TiO2 as scattering medium, and 5% Jeffamine M1000 as dispersant.

[0319] To select a good ligand or co-ligand, several criteria must be met. First, the ligand must protect the ligand on the surface. Second, the ligand must be compatible with the other ink components. Third, the ligand must be air stable by blocking oxygen. To find promising candidates that meet these criteria, co-ligands were added to the ink formulation to create films.

[0320] Figure 11 shows the membrane performance with different ancillary ligands in the ink formulation. The EQE of the membrane was better with ancillary ligand-1 than the others. This is presumably because the bulky end groups of ancillary ligand-1 provide steric hindrance and dense surface passivation on the AIGS nanostructures, which prevents oxygen permeation and oxidation.

[0321] [Table 17]

[0322] Unlike InP, AIGS nanostructures, which can bind well with weakly bound L-type ligands, may reduce the EQE in the presence of active radicals or active species that can cause side reactions. These side reactions are due to radical generation via polymerization initiators or radical active species and photooxidation via oxygen. The stability of the film was confirmed under dark conditions. Under dark conditions, auxiliary ligands-1 and 7 showed very stable EQE compared to the control ink (Figure 11). Ancillary ligand-2 caused a decrease in EQE and was less stable. Therefore, even when the films containing auxiliary ligands-1 and 7 were exposed to air, the films did not deteriorate without exposure to light.

[0323] To confirm the change in the film performance, the photostability was measured under yellow light conditions. As shown in Figure 12, ancillary ligand-1 had better stability to yellow light after 24 hours than the reference ink (control group). Also, phosphorus-based ancillary ligand 7 showed a comparable EQE compared to the reference ink (control group).

[0324] The thermal stability of the membranes was also measured after the membranes were baked at 180° C. As shown in Table 17, the bulky phenol-based ancillary ligand-1 and phosphorus-based ancillary ligand-7 showed better thermal stability compared to the control group.

[0325] [Table 18]

[0326] Also, the ink manufacturing process was modified as shown in Table 18. When the auxiliary ligand-1 was post-added, the EQE was better than that of the reference ligand 1,3-cyclohexanebis(methylamine). Also, when thiol was further added during the ligand exchange with the auxiliary ligand-1, the ink formulation showed the most stable EQE performance. See Figure 13 which shows the temporal stability of the ink and the ink formulation with different ratios of additives when exposed to yellow light conditions.

[0327] [Table 19]

[0328] As shown in Figure 14, additional GaCl3 (S3) treatment of AIGS nanostructures showed improved EQE performance. When inorganic ligand zirconium propoxide (S2) was added together with S3, the performance was further improved. Excessive oxidation of sulfur can be compensated for by adding polyvalent metal-based ligands such as S2. See also Figure 15, which shows that the best performance is obtained for calcined films when co-ligand-1, S2 and S3 are combined. Figure 16 shows that when co-ligand-1, S2 and S3 are combined, the films have high light resistance when exposed to yellow light conditions.

[0329] For comparison, FIG. 17 is a line graph showing EQE % versus blue light absorbance for AIGS films containing 1% S3, 3% S3, and 6% S3.

[0330] While various embodiments have been described above, it should be understood that they have been presented by way of example and not limitation. It will be apparent to those skilled in the relevant art that various changes in form and detail can be made without departing from the spirit and scope of the present invention. Thus, the breadth and scope should not be limited by any of the above-described exemplary embodiments, but should be defined only in accordance with the following claims and their equivalents.

[0331] All publications, patents, and patent applications mentioned in this specification are indicative of the level of those skilled in the art to which this invention pertains, and are herein incorporated by reference to the same extent as if each individual publication, patent, or patent application was specifically and individually indicated to be incorporated by reference.

Claims

1. Ag, In, Ga, and S (AIGS) nanostructures; one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof; At least one ligand A membrane comprising: The film exhibits a photon conversion efficiency (PCE) of greater than 32% at a peak emission wavelength of 480-545 nm when excited using a blue light source having a wavelength of 450 nm, and the PCE of the film is at least 30% after 24 hours under yellow light and air storage conditions. film.

2. 10. The film of claim 1, wherein the nanostructures have an emission spectrum with a full width at half maximum (FWHM) of less than 40 nm.

3. The film of claim 1 or 2, wherein the nanostructures have a quantum yield (QY) of 80-99.9%.

4. The nanostructure has an OD of 0.8 or more. 450 / mass (mL・mg -1 ・cm -1 The membrane according to any one of claims 1 to 3, having a molecular weight of 1.0 or more.

5. The membrane of any one of claims 1 to 4, wherein the nanostructures have an average diameter of less than 10 nm by transmission electron microscopy (TEM).

6. The film of any one of claims 1 to 5, wherein at least 80% of the emission is band edge emission.

7. The membrane according to any one of claims 1 to 6, wherein said at least one ligand is a polyamino ligand.

8. The at least one ligand is a compound of formula I, 【Chemistry 1】 In the formula, x is 1 to 100, y is 0 to 100, and R 2 is C 1~20 The membrane according to any one of claims 1 to 6, wherein the compound is alkyl.

9. The at least one ligand has the formula II: 【Chemistry 2】 In the formula, R 3 and R 4 is independently 3~6 is a secondary or tertiary alkyl group; R 5 is hydrogen or optionally substituted C 1~6 The membrane according to any one of claims 1 to 7, wherein the group is an alkyl group.

10. The one or more metal alkoxides are metal C 1~10 The film of any one of claims 1 to 9, which is an alkoxide and the metal is titanium, zirconium, hafnium, gallium, or barium.

11. The one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or combinations thereof, are selected from the group consisting of zirconium(IV) tetramethoxide, zirconium(IV) tetraethoxide, zirconium(IV) tetra-n-propoxide, zirconium(IV) tetra-isopropoxide, zirconium(IV) tetra-n-butoxide, zirconium(IV) tetra-isobutoxide, zirconium(IV) tetra-n-methyl- pentoxide, zirconium(IV) tetra-isopentoxide, zirconium(IV) tetra-n-hexoxide, zirconium(IV) tetra-isohexoxide, zirconium(IV) tetra-n-heptoxide, zirconium(IV) tetra-isoheptoxide, zirconium(IV) tetra-n-octoxide, zirconium(IV) tetra-n-isooctoxide, zirconium(IV) tetra-n-nonoxide, zirconium(IV) tetra-n-isononoxide, zirconium(IV) tetra-n-decyloxide, or zirconium(IV) tetra-n-isodecyloxide.

12. 12. The membrane of any one of claims 1 to 11, wherein the one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof, is zirconium (IV) tetra-n-propoxide.

13. 2. The membrane of claim 1, wherein the one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof is zirconium (IV) tetra n-propoxide, and the membrane further comprises pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] or 2,4,8,10-tetraoxaspiro[5.5]undecane-3,9-diylbis(2-methylpropane-2,1-diyl)bis[3-[3-(tert-butyl)-4-hydroxy-5-methylphenyl]propanoate].

14. 14. The membrane of any one of claims 1 to 13, wherein the one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or combinations thereof, are present in the composition in an amount of 0.03 to 3.3 wt.%.

15. (a) providing an AIGS nanostructure, one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or a combination thereof, and at least one ligand; (b) combining at least one organic resin with the AIGS nanostructures of (a); (c) preparing a first film on the first barrier layer, the first film comprising the blended AIGS nanostructures, the at least one ligand, and the at least one organic resin; (d) curing the first film; and (e) encapsulating the first film between the first barrier layer and a second barrier layer; 15. A method for preparing the film of any one of claims 1 to 14, comprising:

16. 16. The method of claim 15, wherein the encapsulation of the first film is performed in air prior to exposure to a blue LED light source.

17. 17. The method of claim 16 carried out under an inert atmosphere.

18. 18. The method of claim 17, further comprising adding at least one oxygen-reactive material to the mixture of the AIGS nanostructures of (a), one or more metal alkoxides, one or more metal alkoxide hydrolysis products, one or more metal halides, one or more metal halide hydrolysis products, one or more organometallic compounds, or one or more organometallic hydrolysis products, or combinations thereof, and ligands; adding at least one oxygen-reactive material to the mixture of (b); and / or forming a second film comprising at least one oxygen-reactive material on the first film prepared in (c); and / or forming a sacrificial barrier layer on the first film prepared in (c) that temporarily blocks oxygen and / or water, and measuring the PCE of the film followed by removal of the sacrificial barrier layer.

19. 20. The method of claim 18, wherein the two barrier layers exclude oxygen and / or water.

20. A device comprising a membrane according to any one of claims 1 to 14.

21. (a) a first conductive layer; (b) a second conductive layer; and (c) a film according to any one of claims 1 to 14 between the first conductive layer and the second conductive layer; and 1. A nanostructured shaped article comprising:

22. A backplane; a display panel disposed on the backplane; A film according to any one of claims 1 to 14 disposed on the display panel. A nanostructured color converter comprising:

23. 23. The nanostructure color converter of claim 22, wherein the film comprises patterned AIGS nanostructures.

24. 23. The nanostructure color converter of claim 22, wherein the backplane comprises an LED, an LCD, an OLED, or a microLED.